Aqueous coating material containing cellulose nanofibers

By using polymer binder, cellulose nanofibers and non-polymer polycarboxylic acids in aqueous coating materials, combined with anion-stable polymer binder and polyurethane-polyurea particles, the viscosity instability and storage instability of aqueous coating materials during processing in the ‘wet-pressure-wet’ method is solved, and high angle-allergic color index and good optical and color characteristics are achieved, which are suitable for automotive coatings.

CN119816568APending Publication Date: 2025-04-11BASF COATINGS GMBH
View PDF 24 Cites 0 Cited by

Patent Information

Application Number
CN202380063561.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-05
Filing Date
2023-09-01
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing water-based coating materials have problems such as unstable viscosity, unstable storage and uneven appearance of high angle-dependent different-color index coatings when processed in the 'wet-pressure-wet' method.

Method used

Aqueous coating materials containing polymer binders, cellulose nanofibers and non-polymer polycarboxylic acids are used as the base coating material, combining anionically stable polymer binders and polyurethane-polyurea particles to optimize rheological characteristics and pigment dispersion.

Benefits of technology

It realizes high solid content, good storage stability and viscosity stability of water-based coating materials, and provides high angle-dependent color index and good optical and color characteristics, which are suitable for automotive coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005295801700000281
    Figure BDA0005295801700000281
  • Figure BDA0005295801700000311
    Figure BDA0005295801700000311
  • Figure BDA0005295801700000321
    Figure BDA0005295801700000321
Patent Text Reader

Abstract

The present invention relates to an aqueous coating material comprising one or more polymeric binders; one or more types of cellulose nanofibers; and one or more non-polymeric polycarboxylic acids and / or salts thereof; and optionally comprising one or more pigments. The invention further relates to a wet-press-wet method for producing a multilayer coating system and to a multilayer coating system obtainable according to the method. The invention further relates to the use of an unpigmented aqueous coating material for producing a pigmented aqueous coating material; and the use of at least one type of cellulose nanofibers with one or more non-polymeric polycarboxylic acids and / or salts thereof in aqueous coating materials comprising polymeric binders and pigments, in the production of multilayer coating systems.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to an aqueous coating material containing a polymer binder, which further contains one or more types of cellulose nanofibers and one or more non-polymeric polycarboxylic acids and / or salts thereof. The present invention further relates to a method for producing a multi-layer coating on a substrate, wherein the aqueous coating composition is used as a pigmented basecoat material, preferably in automotive coatings. The present invention further relates to the multi-layer coating system obtained thereby, and furthermore, to the use of cellulose nanofibers and non-polymeric polycarboxylic acids in aqueous coating materials containing polymer binders and pigments, and to the use of the coating material as a basecoat material in the production of a multi-layer coating system. Background Art

[0002] In particular in automotive finishing, but also in other fields where a coating having a good decorative effect and at the same time effective protection against corrosion is desired, it is known practice to provide a substrate with a plurality of coatings arranged one above the other.

[0003] The multicoat paint system is preferably applied by the so-called "wet-on-wet" method, meaning that the pigmented basecoat material is first applied and, after a short flash-off time, is coated again with the clearcoat material without a baking step. Subsequently, the basecoat and the clearcoat are baked together. The "wet-on-wet" method is of particular interest in the application of automotive colors and / or metallic effect paints.

[0004] Economic and environmental reasons have led to the development of multicoat systems using waterborne basecoat materials. The coating materials used to produce these basecoats must be processable by the now customary "wet-on-wet" method; that is, after a very short initial drying period, without a baking step, they must be able to be recoated with a clear topcoat without exhibiting defects in their visual appearance.

[0005] Furthermore, the coating material must also exhibit adequate stability during storage. A customary test is to store the material at 40° C. and subsequently determine any viscosity changes after storage. In particular basecoat materials containing color pigments and / or effect pigments (such as metal effect pigments) should be storage-stable, since otherwise settling of the pigment particles would occur.

[0006] In the case of metallic effect paints for use in the "wet-on-wet" method, there are additional problems that must be solved. The metallic effect depends critically on the dispersion of the metal pigment particles in the coating material, the size and shape of the metal pigment particles, the rheological properties of the coating material, the application of the coating material and the orientation of the metal pigment particles in the coating. Therefore, a metallic effect basecoat material that can be processed by the "wet-on-wet" method must provide a coating in which the metal pigments are present in a favorable spatial orientation after application and in which this orientation is fixed so quickly that it is no longer negatively affected during further finishing operations.

[0007] A suitable parameter for characterizing metallic effect basecoats is light reflection, in particular the directional variation of light reflection, which is typically expressed as an angle-dependent color index. Metallic effect basecoats that exhibit a low angle-dependent color index appear homogeneous when viewed from several angles and on curved surfaces. In order to achieve a low angle-dependent color index, the metallic effect pigments must exhibit a random orientation within the basecoat.

[0008] However, metallic effect basecoats characterized by a high flop index are still gaining popularity. Such coatings present different appearances when viewed from different angles and on curved surfaces. In order to achieve a high flop index, the metallic effect pigments within the basecoat must exhibit an orientation that is essentially parallel to the underlying substrate.

[0009] One way to achieve a high flop index is to manually apply compositions containing metallic effect pigments with a low non-volatile fraction. However, manual application limits the use of such compositions in vehicle production and OEM vehicle finishing.

[0010] Also known from the prior art is the practice of increasing the flop index by adding polyamide waxes with different acid values. For example, EP 0877063 A2, WO 2009 / 100938 A1, EP 2457961 A1 and EP 3183303 A1 describe waterborne coating materials comprising polyamides with an acid value of 30 mg KOH / g polyamide or <10 mg KOH / g polyamide. However, the use of polyamides and other water-insoluble components in waterborne coating materials may lead to incompatibility between these compounds and the water-soluble components of the composition. This particularly leads to granulation processed by the "wet-on-wet" method and / or granulation of the polyamide incorporated into the coating material, and / or insufficient storage stability (demixing or phase separation) of such coating materials, particularly at relatively high temperatures (e.g., temperatures of about 40° C.). In addition, polyamides may lead to poor leveling and / or poor appearance.

[0011] EP 1153989 A1 discloses an aqueous coating material, which comprises a polyamide with an acid value of ≥30 mg KOH / g polyamide and a metal silicate composed of very small, usually nano-scale particles as an additional rheological aid. However, the disadvantage of having such a metal silicate in an aqueous coating material, especially in combination with a polyamide with an acid value of >30 mg KOH / g polyamide, is that it may be generally the appearance of pinholes and / or lumps when processed by means of a "wet-on-wet" method. In addition, the use of metal silicates is undesirable because of their high surface area, and they interact strongly with other formulation components (especially dispersing additives and / or adhesives with pigment-affinity groups). Minimizing these interactions requires a high level of dilution. However, this dilution may particularly adversely affect the shear stability and circulation line stability of the coating material.

[0012] Another method for producing rheologically stable coating materials is disclosed, for example, in US 10,898,923 B2, which describes the use of cellulose nanofibers in aqueous effect pigment formulations. However, these formulations are limited to a maximum solids content of 10% by weight, based on the total weight of the coating material.

[0013] The object of the present invention is to provide an aqueous coating material which allows a solid content of greater than 10% by weight based on the total weight of the coating material. The aqueous coating material should have excellent storage stability and viscosity stability even without the use of a rheology control agent from the group consisting of polyamides and metal silicates. In particular, the aqueous coating material provided by the present invention should be easy to supplement with similar colored pigments and / or effect pigments to form a colored aqueous coating material with storage stability and viscosity stability.

[0014] Furthermore, in particular if used as pigmented basecoat material in a multi-coat coating system, such coating materials should provide the multi-coat coating with good optical and color properties and good leveling properties and, in the case of coating materials containing metallic effect pigments, improved goniochromaticity. Preferably, the aqueous coating materials of the invention are easy to apply in the so-called wet-on-wet coating process and are suitable for use in automotive coatings. Summary of the invention

[0015] These objects are achieved by providing an aqueous coating material comprising

[0016] a) one or more polymer binders

[0017] b) one or more types of cellulose nanofibers; and

[0018] c) one or more non-polymeric polycarboxylic acids and / or salts thereof; and

[0019] d) optionally contains one or more pigments.

[0020] The above-mentioned water-based coating material is also referred to as "the water-based coating material of the present invention" or "the water-based coating material according to the present invention" hereinafter.

[0021] A further subject of the invention is a method for producing a multicoat paint system on a substrate, comprising the following steps:

[0022] (1) optionally producing a cured first coating on a substrate by applying a coating material to the substrate and then curing the composition;

[0023] (2) producing one or more basecoats on the coating obtained in step (1) by applying one or more identical or different aqueous basecoat materials;

[0024] (3) producing one or more clear coat layers by applying a clear coat material over one or the topmost base coat layer; and

[0025] (4) co-curing the one or more basecoats and the one or more clearcoats;

[0026] in

[0027] At least one of the basecoat materials is an aqueous coating material according to the present invention.

[0028] The above-described process for producing a multicoat paint system on a substrate is also referred to hereinafter as "the process of the invention" or "the process according to the invention".

[0029] The invention further provides a multilayer coating system obtainable by the process according to the invention.

[0030] A further subject matter of the present invention is the use of the unpigmented aqueous coating material according to the invention as a universal aqueous coating composition for producing the pigmented aqueous coating material according to the invention.

[0031] Yet another subject of the present invention is the use of at least one type of cellulose nanofibers as used in the aqueous coating material of the present invention together with one or more non-polymeric polycarboxylic acids and / or salts thereof as used in the aqueous coating material of the present invention in an aqueous coating material comprising one or more polymeric binders as in the aqueous coating material of the present invention and one or more pigments as defined above and below for producing a multilayer coating system.

[0032] A further subject matter of the present invention is the use of the pigmented aqueous coating materials of the invention as basecoat materials, preferably in automotive coatings. DETAILED DESCRIPTION

[0033] Water-based coating materials

[0034] The term "coating material" refers to a product in liquid, paste or powder form which, when applied to a substrate, forms a film having protective, decorative and / or other specific properties (DIN ISO 4618:2006). The expression "aqueous coating material" is known to the skilled person. It essentially refers to a liquid coating material whose volatile content is not solely based on organic solvents.

[0035] In fact, any such coating material based on organic solvents contains only organic solvents and no water for dissolving and / or dispersing the components, or is a coating material to which no water is explicitly added during its production, but water enters the composition only in the form of contaminants, atmospheric moisture and / or solvent for any specific additives employed. Such compositions will be referred to as solvent-based or "organic solvent-based" in contrast to waterborne coating materials.

[0036] In the context of the present invention, "aqueous" should preferably be understood as meaning that the coating material comprises a water fraction of at least 20 wt.-%, preferably at least 25 wt.-%, very preferably at least 50 wt.-%, in each case based on the total amount of solvents present (i.e. water and organic solvents). The water fraction is in turn preferably from 60 wt.-% to 100 wt.-%, more particularly from 65 wt.-% to 90 wt.-%, very preferably from 70 wt.-% to 80 wt.-%, in each case based on the total amount of solvents present.

[0037] The coating material of the present invention has a relatively high solid content. Therefore, it is preferred that the composition has a solid content of 10 wt.-% or 11 wt.-% to 65 wt.-%, preferably 15 wt.-% to 50 wt.-%, more particularly 20 wt.-% to 45 wt.-%, in each case based on the total weight of the coating material and according to DIN EN ISO 3251 (June 2008) as described in detail in the Examples section of this specification. In view of the high solid content, the coating material of the present invention has good environmental properties without any adverse effect on its storage stability.

[0038] The coating materials of the invention preferably have a pH, measured in each case at 23° C., in the range from 4 to 10, more preferably in the range from 5 to 10, even more preferably in the range from 7 to 10, more particularly in the range from 7 to 9.

[0039] Preferably, the aqueous coating material of the invention is pigmented and therefore comprises one or more pigments selected from the group consisting of color pigments and effect pigments.

[0040] More preferably, the aqueous coating material of the present invention is a pigmented basecoat material, and is particularly preferably used for automotive coatings.

[0041] Polymer Binders

[0042] The term "binder" in the sense of the present invention and in accordance with DIN EN ISO 4618 (German version, date: March 2007) preferably refers to those non-volatile parts of the composition of the present invention which are responsible for forming the film, excluding any pigments and fillers therein, and more particularly refers to the polymer resin responsible for forming the film. The non-volatile part can be determined by the method described in the Examples section.

[0043] Curing of a coating is therefore understood as the conversion of such a layer into a service-ready state, in other words into a state in which the substrates coated with the coating in question can be transported, stored and used in their intended manner. A cured coating is then in particular no longer soft or tacky, but is conditioned to a solid coating which no longer exhibits any substantial changes in its properties, such as hardness or adhesion to the substrate, even if further exposed to curing conditions as described later below.

[0044] As is known, coating materials can in principle be cured physically and / or chemically, depending on the components present, in particular polymeric binders and crosslinkers, which also belong to the group of binders.

[0045] In the case of chemical curing, thermochemical curing and photochemical-chemical curing are considered. For example, in the case where the coating material is thermochemically curable, it can be self-crosslinked and / or externally crosslinked. In the context of the present invention, the indication that the coating material is self-crosslinked and / or externally crosslinked means that the coating material comprises a polymer as a binder and a crosslinking agent that can be crosslinked accordingly to each other as an adhesive alternatively. The main mechanism and also the adhesive that can be used and the crosslinking agent as a binder (that is, film-forming component) will be described later below.

[0046] In the context of the present invention, "physically curable" or the term "physical curing" means that a cured coating is formed by loss of solvent from a polymer solution or polymer dispersion, wherein curing is achieved, inter alia, by mutual cyclization of polymer chains. These kinds of coating materials are usually formulated as one-component coating materials.

[0047] In the context of the present invention, "thermochemically curable" or the term "thermochemical curing" means the crosslinking of the coating (formation of a cured coating) initiated by a chemical reaction of reactive functional groups, wherein the energetic activation of the chemical reaction may be carried out by thermal energy. Different functional groups that complement each other can react with each other here (complementary functional groups), and / or the formation of a cured coating is based on the reaction of self-reactive groups (in other words, functional groups that react with each other with groups of their own kind). Examples of suitable complementary reactive functional groups and self-reactive functional groups are known, for example, from German patent application DE 199 30 665 A1, page 7, line 28 to page 9, line 24.

[0048] In thermochemically curable one-component systems, the components for crosslinking, such as, for example, an organic polymer as a binder and a crosslinker as a binder, are present alongside one another, in other words in one component. A requirement for this is that the components to be crosslinked—only at relatively high temperatures, for example, typically above 100° C.—effectively react with one another, i.e. enter into a curing reaction. As exemplary combinations, hydroxy-functional polyesters and / or polyurethanes with melamine resins and / or blocked polyisocyanates as crosslinkers may be mentioned.

[0049] In thermochemically curable two-component systems, the components to be crosslinked, such as, for example, an organic polymer as a binder and a crosslinker, are present separately from one another in at least two components, which are not combined until shortly before application. This form is selected when the components for crosslinking undergo an effective reaction with one another even at ambient temperature, such as 20° C. or at slightly elevated temperatures, for example, from 40° C. to 90° C. As exemplary combinations, mention may be made of hydroxy-functional polyesters and / or polyurethanes and / or poly(meth)acrylates with free polyisocyanates as crosslinkers.

[0050] In the context of the present invention, "actinic-chemical curing", or the term "actinic-chemical curing" refers to the fact that curing is also possible by applying actinic radiation (this is electromagnetic radiation, such as near infrared (NIR) and UV radiation, more particularly UV radiation) and also particulate radiation (such as electron beams). Curing by UV radiation is usually initiated by free radical or cationic photoinitiators. Typical actinic curable functional groups are carbon-carbon double bonds, in which case free radical photoinitiators are usually used. Therefore, actinic curing is likewise based on chemical crosslinking.

[0051] Of course, in the solidification of the coating material that is identified as chemically curable, there will always be physical solidification, in other words, the mutual ringing of polymer chains. Physical solidification can even be dominant. However, as long as it includes at least a portion of a chemically curable film-forming component, this type of coating material is identified as chemically curable.

[0052] In the case of purely physically curable coating materials, curing is preferably carried out between 15° C. and 90° C. over a period of 2 to 48 hours. In this case, curing differs from flash evaporation and / or intermediate drying, where appropriate, only in the duration of the coating conditioning. In addition, it is unwise to distinguish between flash evaporation and intermediate drying. For example, for a coating produced by applying a physically curable coating material, it will be possible to first undergo flash evaporation or intermediate drying at 15° C. to 35° C. for a duration of, for example, 0.5 to 30 minutes, and then undergo curing at 50° C. for a duration of 5 hours.

[0053] In principle, and in the context of the present invention, the curing of thermochemically curable one-component systems can preferably be carried out at a temperature of 100° C. to 250° C., preferably 100° C. to 180° C., for a duration of 5 to 60 minutes, preferably 10 to 45 minutes, since these conditions are generally necessary for the chemical crosslinking reaction to convert the coating into a cured coating. It is therefore the case that the flashing and / or intermediate drying phases carried out before the curing are carried out at lower temperatures and / or for shorter times. In this case, for example, the flashing can be carried out at 15° C. to 35° C., for a duration of, for example, 0.5 to 30 minutes, and / or the intermediate drying can be carried out at a temperature of, for example, 40° C. to 90° C., for a duration of, for example, 1 to 60 minutes.

[0054] In principle, and in the context of the present invention, the curing of thermochemically curable two-component systems is carried out at a temperature of 15° C. to 90° C., for example, in particular 40° C. to 90° C., for a duration of 5 to 80 minutes, preferably 10 to 50 minutes. It is therefore the case that the flash evaporation and / or intermediate drying phase carried out before the curing is carried out at a lower temperature and / or for a shorter time. In this case, for example, it is no longer sensible to distinguish between the concepts of flash evaporation and intermediate drying. The flash evaporation or intermediate drying phase before the curing can be carried out, for example, at 15° C. to 35° C., for a duration of, for example, 0.5 to 30 minutes, but at least at a lower temperature and / or for a shorter time than the subsequent curing.

[0055] Of course, this does not exclude that thermochemically curable two-component systems are cured at higher temperatures. For example, in the wet-on-wet coating method of the invention, as described more precisely later below, the basecoat or two or more basecoats are cured together with the clearcoat. For example, when both thermochemically curable one-component systems and two-component systems are present in the layer (e.g. one-component basecoat material and two-component clearcoat material), the co-curing is of course guided by the curing conditions necessary for the one-component system.

[0056] All temperatures stated in the context of the present invention are to be understood as the temperature of the chamber that the coated substrate is located in. Therefore, this does not mean that it is required that the substrate itself has the temperature in question.

[0057] Since the aqueous coating materials of the present invention may use different curing mechanisms, the one or more polymer binders PB as used in the coating materials of the present invention may differ in their composition.

[0058] Thus, the one or more polymer binders PD of the present invention may be selected from the group consisting of physically drying polymer binders, thermochemically curable binders and / or radiation curable binders.

[0059] In particular, the one or more polymer binders PB are preferably nonionic and / or anionically stabilized polymer binders. However, anionically stabilized polymer binders are more preferred as one or more polymer binders PB as used in the aqueous coating material of the present invention.

[0060] Non-ionically stabilized polymer binder

[0061] Typically, nonionic stabilization of the polymer binder in the aqueous coating composition is achieved by introducing a water-soluble nonionic moiety into the polymer binder. Such moieties are preferably selected from the group comprising or consisting of a poly(oxyalkylene) moiety, a polylactone moiety such as a polybutyrolactone moiety, a polyol moiety such as a polyvinyl alcohol moiety and also a polyvinylpyrrolidone moiety, more particularly a poly(oxyethylene) moiety and / or a poly(oxypropylene) moiety.

[0062] Anionically stabilized polymer binder

[0063] Anionic stabilization of the polymeric binder in the aqueous coating composition is typically achieved by introducing anionic groups into the polymeric binder.Such anionic groups are preferably introduced in the form of acidic groups such as carboxylic acid groups, and the acidic groups are subsequently at least partially neutralized.

[0064] In the waterborne coating materials of the present invention, anionically stabilized polymer binders are superior to nonionically stabilized polymer binders because their use in combination with cellulose nanofibers and non-polymeric polycarboxylic acids produces multilayer coatings with even better color matching and flop properties.

[0065] Particularly preferably, an anion-stabilized polymer binder is used which has a certain electrophoretic mobility at a pH of 8.0. Electrophoretic mobility can be determined as described in the Examples section herein. Therefore, in a preferred embodiment of the invention, at least one anion-stabilized polymer binder has an electrophoretic mobility of -2.5 to -15 (μm / s) / (V / cm), preferably -2.5 to -10 (μm / s) / (V / cm), more preferably -4 to -8 (μm / s) / (V / cm), more particularly -5 to -8 (μm / s) / (V / cm) at a pH of 8.0.

[0066] Furthermore, it is advantageous if the anionically stabilized polymer binder is present in the aqueous coating composition of the invention in a defined total amount. Thus, in a preferred embodiment of the invention, at least one anionically stabilized polymer binder is present in a total amount of 20 wt.-% to 80 wt.-%, preferably 30 wt.-% to 70 wt.-%, more particularly 40 wt.-% to 70 wt.-%, in each case based on the total solids content of the coating composition. If more than one anionically stabilized polymer binder is used, the above-mentioned amount ranges are based on the total amount of anionically stabilized polymer binder in the composition. The use of at least one anionically stabilized polymer binder in combination with one or more cellulose nanofibers and one or more non-polymeric polycarboxylic acids within the above-mentioned amount ranges leads to particularly good flop indexes and also good optical and color properties in the pigmented aqueous basecoat without adversely affecting the storage stability of the composition of the invention. Furthermore, the use of the above-mentioned amounts of anionically stabilized polymer binder leads to effective fixation of the orientation of the effect particles in the effectively pigmented aqueous basecoat formed from the aqueous coating composition of the invention containing effect pigments during flash evaporation, and thus the subsequent application of a further coating composition has no adverse effect on the orientation of the effect particles and thus on the flop index.

[0067] Polyurethane-polyurea-granules (PPP)

[0068] In the context of the present invention, it has proven advantageous if the anionically stabilized polymer binder comprises anionically stabilized polyurethane-polyurea particles (PPP) dispersed in water.

[0069] The anionically stabilized polymer binder therefore preferably comprises anionically stabilized polyurethane-polyurea particles (PPP) dispersed in water and having an average particle size of preferably 40 to 2000 nm and a gel fraction of at least 50%, the anionically stabilized polyurethane-polyurea particles (PPP) comprising in each case in reacted form:

[0070] (Z.1.1) at least one isocyanate group-containing polyurethane prepolymer which contains groups which are anionic groups and / or can be converted into anionic groups, and

[0071] (Z.1.2.) At least one polyamine containing two primary amino groups and one or two secondary amino groups.

[0072] The anionically stabilized polyurethane-polyurea particles (PPP) are dispersed in water or are present in the form of an aqueous dispersion. The fraction of water in the dispersion is preferably 45 wt.-% to 75 wt.-%, preferably 50 wt.-% to 70 wt.-%, more preferably 55 wt.-% to 65 wt.-%, in each case based on the total amount of the dispersion. It is preferred that the dispersion consists to a certain extent of at least 90 wt.-%, preferably at least 92.5 wt.-%, very preferably at least 95 wt.-% and more preferably at least 97.5 wt.-% of polyurethane-polyurea particles (PPP) and water (the relevant value is obtained by summing the amount of particles (i.e. the amount of polymer determined via the solids content) and the amount of water).

[0073] Anionically stabilized polyurethane-polyurea particles (PPP) are polymer particles based on polyurethane-polyurea. Anionically stabilized polyurethane-polyurea particles (PPP) preferably have a gel fraction of at least 50% (for measurement methods, see the Examples section), and preferably have an average particle size (average particle size) (also referred to as average particle size) of 40 to 2000 nanometers (nm) (for measurement methods, see the Examples section). Therefore, polyurethane-polyurea particles (PPP) constitute microgels. The reason is that, on the one hand, the polymer particles are in the form of relatively small particles or microparticles, and on the other hand, they are at least partially intramolecularly crosslinked. The latter means that the polymer structure present in the particles is equivalent to a typical macroscopic network with a three-dimensional network structure. However, macroscopically, this type of microgel still contains discrete polymer particles.

[0074] Since microgels represent structures intermediate between branched and macro-crosslinked systems, they combine the features of macromolecules with a network structure that are soluble in a suitable organic solvent and of an insoluble macro-network, and the fraction of crosslinked polymer can therefore only be determined, for example, after separation of the solid polymer, removal of water and any organic solvent and subsequent extraction. The phenomenon utilized here is that the microgel particles, which are initially soluble in a suitable organic solvent, retain their internal network structure after separation and behave like a macro-network in the solid. Crosslinking can be verified via the experimentally obtainable gel fraction. Finally, the gel fraction is the fraction of polymer in the microgel that cannot be dispersedly dissolved in the solvent as isolated solid molecules. It is necessary here to exclude a further increase in the gel fraction caused by crosslinking reactions after separation of the polymer solid. This insoluble fraction in turn corresponds to the fraction of polymer present in the form of intramolecularly crosslinked particles or granular parts.

[0075] The polyurethane-polyurea particles (PPP) preferably have a gel fraction of 50%, preferably at least 60%, more preferably at least 70%, more particularly at least 80%. Thus, the gel fraction may be up to 100% or close to 100%, such as, for example, 99% or 98%. In this case, the entire, or almost the entire, polyurethane-polyurea polymer is in the form of crosslinked particles.

[0076] The polyurethane-polyurea particles (PPP) have an average particle size of 40 to 2000 nm, preferably 40 to 1500 nm, more preferably 100 to 1000 nm, still more preferably 110 to 500 nm, more particularly 120 to 300 nm. An especially preferred range is from 130 to 250 nm.

[0077] The polyurethane-polyurea particles (PPP) comprise in each case in reacted form:

[0078] (Z.1.1) at least one polyurethane prepolymer which contains isocyanate groups and contains groups which are anionic groups and / or can be converted into anionic groups, and also

[0079] (Z.1.2) At least one polyamine containing two primary amino groups and one or two secondary amino groups.

[0080] The expression "polyurethane-polyurea particles (PPP) comprise in each case in reacted form a polyurethane prepolymer (Z.1.1) and a polyamine (Z.1.2)" here means that the aforementioned NCO-containing polyurethane prepolymer (Z.1.1) and also a polyamine (Z.1.2) are used in the preparation of the polyurethane-polyurea particles (PPP), and these two components react with one another to form urea compounds.

[0081] The polyurethane-polyurea particles (PPP) preferably consist of these two components (Z.1.1) and (Z.1.2), meaning that they are prepared from these two components. The polyurethane-polyurea particles (PPP) dispersed in water can be obtained, for example, by a specific three-stage process.

[0082] In the first step (I) of the process, a composition (Z) is prepared.

[0083] The composition (Z) comprises at least one, preferably exactly one, specific intermediate (ZL) containing isocyanate groups and blocked primary amino groups. The preparation of the intermediate (Z.1) comprises reacting at least one polyurethane prepolymer (Z.1.1) containing isocyanate groups and groups as anionic groups and / or groups which can be converted into anionic groups with at least one compound (Z.1.2a) which is derived from a polyamine (Z.1.2) and contains at least two blocked primary amino groups and at least one free secondary amino group.

[0084] For the purposes of the present invention, component (Z.1.1) is referred to as a prepolymer for ease of understanding.

[0085] The prepolymer (Z.1.1) contains groups which are anionic groups and / or can be converted into anionic groups (i.e. groups which can be converted into anionic groups by using known and also later specified neutralizing agents (such as bases) below). As known to the skilled person, these groups are, for example, carboxylic acid groups, sulfonic acid groups and / or phosphonic acid groups, more particularly carboxylic acid groups (functional groups which can be converted into anionic groups by neutralizing agents), and also anionic groups derived from the above functional groups, such as more particularly carboxylate, sulfonate and / or phosphonate groups, preferably carboxylate groups. It is known to introduce such groups to increase dispersibility in water. Depending on the conditions selected, the groups can be present in one form (e.g., carboxylic acid) or in another form (carboxylate), for example, proportionally or almost completely by using a neutralizing agent described later below.

[0086] To introduce the groups, during the preparation of the prepolymer (Z.1.1), starter compounds can be used which, in addition to the groups (preferably hydroxyl groups) used for the reaction in the preparation of the urethane bonds, further contain the above-mentioned groups (e.g. carboxylic acid groups). In this way, the groups in question are introduced into the prepolymer.

[0087] Corresponding compounds envisaged for the introduction of preferred carboxylic acid groups include - as long as they contain carboxyl groups - polyether polyols and / or polyester polyols. However, preference is given to using low molecular weight compounds which in any case have at least one carboxylic acid group and at least one functional group reactive toward isocyanate groups, preferably a hydroxyl group. The expression "low molecular weight compound" in the context of the present invention means that the compound in question has a molecular weight of less than 300 g / mol. A range from 100 to 200 g / mol is preferred. Examples of preferred compounds in this sense are monocarboxylic acids containing, for example, two hydroxyl groups, such as dihydroxypropionic acid, dihydroxysuccinic acid and dihydroxybenzoic acid. More particularly, they are α,α-dimethylolalkanoic acids, such as 2,2-dimethylolacetic acid, 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid and 2,2-dimethylolpentanoic acid, especially 2,2-dimethylolpropionic acid.

[0088] The prepolymers (Z.1.1) therefore preferably contain carboxylic acid groups. Based on the solids content, they preferably have an acid number of 10 to 30 mg KOH / g, more particularly 15 to 23 mg KOH / g (for the measurement method, see the Examples section).

[0089] The prepolymer (Z.1.1) is preferably prepared by reaction of a diisocyanate with a polyol. Examples of suitable polyols are saturated or ethylenically unsaturated polyester polyols and / or polyether polyols, as described, for example, in WO 2018 / 011311 A1 and WO 2016 / 091546 A1. Polyols preferably used for the preparation of the prepolymer (Z.1.1) are polyester diols prepared using dimer fatty acids. Particularly preferred are polyester diols prepared using dicarboxylic acids, wherein at least 50 wt.-%, preferably 55 wt.-% to 75 wt.-% of the dicarboxylic acids used are dimer fatty acids.

[0090] Dimer fatty acids are oligomers of unsaturated monomeric fatty acid forms. The fatty acids are saturated or unsaturated, in particular unbranched monocarboxylic acids having 8 to 64 carbon atoms.

[0091] In addition, in order to prepare the polymer (Z.1.1), polyamines such as diamines and / or amino alcohols can also be used. Examples of diamines include hydrazine, alkyl diamines or cycloalkyl diamines such as propylene diamine and 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, and examples of amino alcohols include ethanolamine or diethanolamine.

[0092] With regard to polyisocyanates suitable for preparing polyurethane prepolymers containing isocyanate groups (Z.1.1), reference is made to the published specifications WO 2018 / 011311 A1 and WO 2016 / 091546 A1. Aliphatic diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate (IPDI), dicyclohexylmethane 4,4′-diisocyanate, 2,4- or 2,6-diisocyanato-1-methylcyclohexane and / or meta-tetramethylene xylene diisocyanate (m-TMXDI) are preferably used.

[0093] The number average molecular weight of the prepolymers can vary widely and lies, for example, in the range from 2000 to 20 000 g / mol, preferably from 3500 to 6000 g / mol (for measurement methods, see the Examples section).

[0094] The prepolymer (Z.1.1) contains isocyanate groups and preferably has an isocyanate content of 0.5 to 6.0 wt.-%, preferably 1.0 to 5.0 wt.-%, particularly preferably 1.5 to 4.0 wt.-%, based on the solids content (for the measurement method, see the Examples section).

[0095] The hydroxyl value of the prepolymer is preferably less than 15 mg KOH / g, more particularly less than 10 mg KOH / g, still more preferably less than 5 mg KOH / g, based on the solids content (for the measurement method, see the Examples section).

[0096] The prepolymer (Z.1.1) can be prepared as described in WO 2018 / 011311 A1 and WO 2016 / 091546 A1.

[0097] As already indicated above, groups which are present in the prepolymer (Z.1.1) and which can be converted into anionic groups can also be present in proportion as anionic groups, for example by using neutralizing agents. In this way, the water dispersibility of the prepolymer (Z.1.1) and therefore also the intermediate (Z.1) can be adjusted. Contemplated neutralizing agents include in particular the known alkaline neutralizing agents, such as, for example, carbonates, bicarbonates or hydroxides of alkali metals and alkaline earth metals, such as, for example, LiOH, NaOH, KOH or Ca(OH)2. Also suitable for neutralization and preferably used in the context of the present invention are organic nitrogenous bases, such as amines, such as ammonia, trimethylamine, triethylamine, tributylamine, dimethylaniline, triphenylamine, dimethylethanolamine, methyldiethanolamine or triethanolamine, and also mixtures thereof.

[0098] If it is desired to neutralize groups - in particular carboxylic acid groups - which can be converted into anionic groups, the neutralizing agent can be added, for example, in an amount such that a fraction of 35% to 65% of the groups are neutralized (neutralization degree). A range from 40% to 60% is preferred (for calculation method, see the Examples section).

[0099] Compound (Z.1.2a) contains two blocked primary amino groups and one or two free secondary amino groups.

[0100] As known, blocked amino groups are those in which the hydrogen groups on the nitrogen inherently present in the free amino group have been replaced by a reversible reaction with a blocking agent. In view of blocking, the amino group cannot react via condensation or addition reactions like the free amino group, and is therefore non-reactive in this respect and therefore different from the free amino group. The primary amino group of compound (Z.1.2a) can be blocked with a blocking agent known per se (such as, for example, with ketones and / or aldehydes). In the case of such blocking, ketimines and / or aldimines are produced, and water is released. This type of group can be unblocked by adding water.

[0101] If the amino group is specified neither as blocked nor as free, reference is made to the free amino group.

[0102] Preferred blocking agents for the primary amino groups of the blocking compounds (Z.1.2a) are ketones. Particularly preferred among these ketones are those which are organic solvents (Z.2) as described later below. The reason is that the solvent (Z.2) must in any case be present in the composition (Z) to be prepared in stage (I) of the method. Therefore, by using ketones (Z.2) for blocking, the corresponding preferred production methods for blocking amines can be adopted without having to separate out the possibly undesirable blocking agents in a costly and inconvenient manner. Instead, the solution of the blocked amine can be used directly for the preparation of the intermediate (Z.1). Preferred blocking agents are acetone, methyl ethyl ketone, methyl isobutyl ketone, diisopropyl ketone, cyclopentanone or cyclohexanone; particularly preferred are the ketones (Z.2) methyl ethyl ketone and methyl isobutyl ketone.

[0103] The preferred blocking with ketones and / or aldehydes, in particular ketones, and the related preparation of ketimines and / or aldimines have the advantage that, among other things, primary amino groups are blocked selectively. The secondary amino groups present are obviously not blocked and therefore remain free. Thus, by means of the preferred blocking reaction described from the corresponding polyamines (Z.1.2) containing free secondary and primary amino groups, compounds (Z.1.2a) which contain one or two free secondary amino groups in addition to the two blocked primary amino groups can be easily prepared.

[0104] The compound (Z.1.2a) preferably has two blocked primary amino groups and one or two free secondary amino groups, and the primary amino groups it has are exclusively blocked primary amino groups, and the secondary amino groups it has are exclusively free secondary amino groups.

[0105] Compound (Z.1.2a) preferably has a total of three or four amino groups which are selected from the group of blocked primary amino groups and free secondary amino groups.

[0106] Particularly preferred compounds (Z.1.2a) are those which consist of two terminal primary amino groups, one or two free secondary amino groups and also aliphatic saturated hydrocarbon groups.

[0107] Similar preferred embodiments are valid for polyamines (Z.1.2), which then contain free primary amino groups instead of blocked primary amino groups. Examples of preferred polyamines (Z.1.2) which can also be prepared by blocking primary amino groups are diethylenetriamine, 3-(2-aminoethyl)aminopropylamine, dipropylenetriamine, and also N1-(2-(4-(2-aminoethyl)piperazin-1-yl)ethyl)-ethane-1,2-diamine (one secondary amino group, two primary amino groups to be blocked) and triethylenetetramine, and also N,N′-bis(3-aminopropyl)ethylenediamine (two secondary amino groups, two primary amino groups to be blocked).

[0108] If a certain amount of the polyamine is blocked, the blocking may result in, for example, a 95 mol % or greater fraction of the primary amino groups being blocked (this fraction can be determined by IR spectroscopy; see the Examples section). For example, in the case of a polyamine in the unblocked state having two free primary amino groups, and then in the case of a certain amount of the primary amino groups of this amine being blocked, in the context of the present invention, it is said that the amine has two blocked primary amino groups if a fraction of more than 95 mol % of the primary amino groups in the amount employed is blocked.

[0109] The preparation of the intermediate (Z.1) involves reacting the prepolymer (Z.1.1) with the compound (Z.1.2a) by an addition reaction of the isocyanate groups from (Z.1.1) with the free secondary amino groups from (Z.1.2a). This reaction (which is known per se) then results in the attachment of the compound (Z.1.2a) to the prepolymer (Z.1.1) to form a urea bond, ultimately giving the intermediate (Z.1).

[0110] Intermediate (Z.1) can be prepared as described in WO 2018 / 011311 A1 and WO 2016 / 091546 A1.

[0111] The fraction of intermediate (Z.1) is from 15 wt.-% to 65 wt.-%, preferably from 25 wt.-% to 60 wt.-%, more preferably from 30 wt.-% to 55 wt.-%, particularly preferably from 35 wt.-% to 52.5 wt.-% and in a very specific embodiment from 40 wt.-% to 50 wt.-%, in each case based on the total amount of composition (Z).

[0112] The composition (Z) further comprises at least one specific organic solvent (Z.2). At a temperature of 20° C., the solvent (Z.2) has a solubility in water of at most 38 wt.-%. (For the measurement method, see the Examples section). The solubility in water at a temperature of 20° C. is preferably less than 30 wt.-%. A preferred range is from 1 wt.-% to 30 wt.-%. Therefore, the solvent (Z.2) has a rather moderate solubility in water and more particularly is not completely miscible with water or does not have an infinite solubility in water.

[0113] Examples of solvents (Z.2) are methyl ethyl ketone, methyl isobutyl ketone, diisobutyl ketone, ethyl ether, butyl ether, dipropylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, methyl acetate, ethyl acetate, butyl acetate, propylene carbonate, cyclohexanone, or mixtures of these solvents. Preference is given to methyl ethyl ketone, which has a solubility in water of 24 wt.-% at 20° C. Thus, none of the solvents (Z.2) are solvents such as acetone, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, tetrahydrofuran, dioxane, N-formylmorpholine, dimethylformamide or dimethyl sulfoxide.

[0114] The effect of choosing a specific solvent (Z.2) which has only limited water solubility is in particular that when dispersing the composition (Z) in the aqueous phase (which occurs in step (II) of the process), no homogeneous solution is formed directly; instead, the crosslinking reaction (addition reaction of free primary amino groups and isocyanate groups to form urea bonds) which occurs in step (II) takes place in a restricted volume, thus enabling the formation of microparticles as defined above.

[0115] The fraction of the at least one organic solvent (Z.2) is from 35 wt.-% to 85 wt.-%, preferably from 40 wt.-% to 75 wt.-%, more preferably from 45 wt.-% to 70 wt.-%, particularly preferably from 47.5 wt.-% to 65 wt.-% and in a very specific embodiment from 50 wt.-% to 60 wt.-%, in each case based on the total amount of composition (Z).

[0116] In the present invention, it has emerged that as a result of the combination of the selection of the intermediate (Z.1) and the specific solvent (Z.2) in the composition (Z) as specified above, a polyurethane-polyurea dispersion comprising polyurethane-polyurea particles (PPP) having the desired particle size and gel fraction can be provided according to steps (II) and (III) described below.

[0117] The described components (Z.1) and (Z.2) preferably account for at least 90 wt.-% of the composition (Z) in total. These two components preferably account for at least 95 wt.-%, more particularly at least 97.5 wt.-% of the composition (Z). Very particularly preferably, the composition (Z) consists of these two components. In this context, it can be noted that when using neutralizing agents as described above, these neutralizing agents are included in the intermediate when calculating the amount of the intermediate (Z.1). Therefore, the solid content of the composition (Z) preferably corresponds to the fraction of the intermediate (Z.1) in the composition (Z). Therefore, the composition (Z) preferably has a solid content of 15 wt.-% to 65 wt.-%, preferably 25 wt.-% to 60 wt.-%, more preferably 30 wt.-% to 55 wt.-%, particularly preferably 35 wt.-% to 52.5 wt.-% and in a very specific embodiment from 40 wt.-% to 50 wt.-%.

[0118] Particularly preferred compositions (Z) therefore comprise in total at least 90 wt.-% of components (Z.1) and (Z.2) and, apart from the intermediate (Z.1), exclusively organic solvents.

[0119] In step (II) of the process described here, the composition (Z) is then dispersed in water, accompanied by unblocking of the blocked primary amino groups of the intermediate (Z.1) and reaction of the resulting free primary amino groups with the isocyanate groups of the intermediate (Z.1) and also with the isocyanate groups of the unblocked intermediate generated from the intermediate (Z.1), the reaction being an addition reaction.

[0120] Step (II) of the method of the present invention can be carried out as described in WO 2018 / 011311 A1 and WO 2016 / 091546 A1.

[0121] The fraction of polyurethane-polyurea particles (PPP) in the dispersion is preferably 25 wt.-% to 55 wt.-%, preferably 30 wt.-% to 50 wt.-%, more preferably 35 wt.-% to 45 wt.-%, in each case based on the total amount of the dispersion (determined analogously to the solids content determination as described above for intermediate (Z.1)).

[0122] The polyurethane-polyurea particles (PPP) preferably have an acid number of 10 to 35 mg KOH / g, more particularly 15 to 23 mg KOH / g (for the measurement method, see the Examples section). In addition, the polyurethane-polyurea particles have very few or no hydroxyl groups. Thus, the OH number of the particles is less than 15 mg KOH / g, more particularly less than 10 mg KOH / g, more preferably less than 5 mg KOH / g (for the measurement method, see the Examples section).

[0123] Anionically stabilized polyurethane-polyurea particles (PPP) dispersed in water preferably have an electrophoretic mobility of -6 to -8 (μm / s) / (V / cm) at a pH of 8.0.

[0124] Furthermore, the coating composition may comprise anionically stabilized polyurethane-polyurea particles (PPP) in a total amount of 10 wt.-% to 50 wt.-%, preferably 20 wt.-% to 45 wt.-%, more particularly 23 wt.-% to 40 wt.-%, in each case based on the total solids content of the coating composition. The use of anionically stabilized polyurethane-polyurea particles (PPP) in the above-mentioned total amounts in combination with at least one non-polymeric polycarboxylic acid leads to a high flop index. Furthermore, the use of such a binder leads to an effective fixation of the oriented effect particles EP during the flash evaporation of the coating composition of the invention and thus does not negatively affect the high flop index even when applying further layers of the coating composition.

[0125] Other anion-stabilized polymers (asP)

[0126] According to the invention, it may be advantageous to use anionically stabilized polymers (asP) as anionically stabilized polymer binders in addition to or instead of the above-mentioned anionically stabilized polyurethane-polyurea particles (PPP).

[0127] Particularly preferably, the composition of the present invention comprises at least two mutually different anionically stabilized polymer binders, wherein the first anionically stabilized polymer binder is the above-mentioned anionically stabilized polyurethane-polyurea particles (PPP) and the second anionically stabilized polymer binder is the anionically stabilized polymer (asP) described below.

[0128] In the context of the present invention, it therefore proves to be advantageous if the at least one anionically stabilized polymer binder is an anionically stabilized seed-core-shell polymer (asP) dispersed in water. It is therefore particularly preferred according to the invention if the at least one anionically stabilized polymer binder comprises at least one anionically stabilized polymer (asP) dispersed in water and having an average particle size of 100 to 500 nm, the preparation of the anionically stabilized polymer (asP) comprising a continuous free radical emulsion polymerization of three mixtures (A), (B) and (C) of ethylenically unsaturated monomers, wherein

[0129] o the mixture (A) comprises at least 50 wt.-% of vinyl aromatic monomers, and the polymer prepared from the mixture (A) has a glass transition temperature of from 10° C. to 65° C.,

[0130] o the mixture (B) comprises at least one polyunsaturated monomer, and the polymer prepared from the mixture (B) has a glass transition temperature of -35°C to 15°C, and

[0131] o the mixture (C) comprises at least one anionic monomer, and the polymer prepared from the mixture (C) has a glass transition temperature of -50°C to 15°C,

[0132] And among them

[0133] i. firstly polymerizing the mixture (A),

[0134] ii. then polymerizing the mixture (B) in the presence of the polymer prepared according to i., and

[0135] iii. Thereafter the mixture (C) is polymerized in the presence of the polymer prepared according to ii.

[0136] The glass transition temperature was determined as detailed in the Examples section.

[0137] The anionically stabilized polymer (asP) is dispersed in water. The anionically stabilized polymer (asP) is therefore in the form of an aqueous dispersion. In this context, the expression "dispersed in water or aqueous dispersion" is known to the skilled person. It fundamentally refers to systems whose dispersion medium does not only or predominantly contain organic solvents (also called solvents) but rather contains a significant fraction of water. The aqueous dispersion preferably contains a water fraction of 55 wt.-% to 75 wt.-%, particularly preferably 60 wt.-% to 70 wt.-%, in each case based on the total weight of the dispersion.

[0138] It is preferred that exactly one of the above polymers (asP) is dispersed in water. The preparation of the anionically stabilized polymer (asP) comprises the continuous free radical emulsion polymerization of three mixtures of ethylenically unsaturated monomers (A), (B) and (C) using a water-soluble initiator, as described, for example, in WO 2017 / 088988 A1.

[0139] The individual polymerization stages in the preparation of the anionically stabilized polymers (asP) can be carried out, for example, as a so-called "starve feed" polymerization (also called "starve feed" or "starve fed" polymerization). In the sense of the present invention, a starve feed polymerization is an emulsion polymerization in which the amount of free ethylenically unsaturated monomers in the reaction solution (also called reaction mixture) is minimized over the entire reaction time. This means that the ethylenically unsaturated monomers are metered in such a way that over the entire reaction time, the fraction of free monomers in the reaction solution does not exceed 6.0 wt.-%, preferably 5.0 wt.-%, more preferably 4.0 wt.-%, particularly advantageously 3.5 wt.-%, in each case based on the total amount of monomers used in the respective polymerization stage.

[0140] The concentration of monomers in the reaction solution can be determined by gas chromatography, for example, as described in publication WO 2017 / 088988 A1. The fraction of free monomers can be controlled by the interaction of the initiator dosage, the initiator addition rate, the monomer addition rate and by the choice of monomers. Not only slowing down the metering, but also increasing the initial amount, and also starting to add the initiator too early, all help to keep the concentration of free monomers below the above limit value.

[0141] For the purposes of the present invention, it is preferred to carry out polymerization stages ii. and iii. under starved feed conditions. This has the advantage that the formation of new particle cores within these two polymerization stages is effectively minimized. In contrast, the particles present after stage i. (and therefore also referred to below as seeds) can be grown further in stage ii. by polymerization of monomer mixture B (therefore also referred to below as cores). It is likewise possible that the particles present after stage ii. (also referred to below as polymer comprising seeds and cores) are grown further in stage iii. by polymerization of monomer mixture C (therefore also referred to below as shells), ultimately resulting in a polymer comprising particles comprising seeds, cores and shells. Stage i. can of course also be carried out under starved feed conditions.

[0142] The mixtures (A), (B) and (C) are mixtures of ethylenically unsaturated monomers and the mixtures (A), (B) and (C) are different from one another. Therefore, they each contain different monomers and / or different proportions of at least one of the defined monomers. The fractions of the monomer mixtures are preferably matched to one another as follows. The fraction of the mixture (A) is from 0.1 wt.-% to 10 wt.-%, the fraction of the mixture (B) is from 60 wt.-% to 80 wt.-% and the fraction of the mixture (C) is from 10 wt.-% to 30 wt.-%, in each case based on the sum of the individual amounts of the mixtures (A), (B) and (C).

[0143] The mixture (A) comprises at least 50 wt.-%, in particular at least 55 wt.-%, of vinylaromatic compounds. One such preferred monomer is styrene. Apart from the vinylaromatic compounds, the mixture (A) contains no monomers having functional groups containing heteroatoms. Particularly preferably, the monomer mixture (A) comprises at least one monounsaturated ester of (meth)acrylic acid having an alkyl group and at least one monoethylenically unsaturated monomer containing a vinyl group, wherein the radical arranged on the vinyl group is an aromatic or mixed saturated aliphatic-aromatic radical, in which case the aliphatic part of the radical is an alkyl group.

[0144] The monomers present in mixture (A) are chosen such that the polymer prepared therefrom has a glass transition temperature of 10 to 65° C., preferably 30 to 50° C. For a useful estimate of the glass transition temperature to be expected in the measurements, the Fox equation known to the skilled person can be employed.

[0145] The polymer prepared in stage i. by emulsion polymerization of the monomer mixture (A) preferably has a particle size of 20 to 125 nm (for the measurement of the particle size, see the Examples section).

[0146] The mixture (B) comprises at least one polyethylenically unsaturated monomer, preferably at least one diethylenically unsaturated monomer, in particular exclusively diethylenically unsaturated monomers. One such preferred monomer is 1,6-hexanediol diacrylate. Preferably, the monomer mixture (B) likewise contains no monomers having functional groups containing heteroatoms. Particularly preferably, the monomer mixture (B) comprises, in addition to at least one polyethylenically unsaturated monomer, at least the following further monomers. Firstly, at least one monounsaturated ester of (meth)acrylic acid having an alkyl group, and secondly at least one monoethylenically unsaturated monomer containing a vinyl group, wherein the group arranged on the vinyl group is aromatic or a mixed saturated aliphatic-aromatic group, in which case the aliphatic part of the group is an alkyl group.

[0147] The fraction of the polyunsaturated monomer is preferably from 0.05 mol % to 3 mol %, based on the total molar amount of the monomers in the monomer mixture (B).

[0148] The monomer mixtures (A) and (B) are preferably free of hydroxy-functional monomers and free of acid-functional monomers. Thus, the monomer mixtures (A) and (B) contain 0 wt.-% of hydroxy-functional monomers and acid-functional monomers, based on the sum of the individual amounts of mixtures (A), (B) and (C).

[0149] The monomers present in mixture (B) are chosen such that the polymer prepared therefrom has a glass transition temperature of from -35°C to 15°C, preferably from -25°C to +7°C.

[0150] The polymer obtained after stage ii. preferably has a particle size ranging from 80 to 280 nm, preferably from 120 to 250 nm.

[0151] The monomers present in mixture (C) are chosen such that the polymers prepared therefrom have a glass transition temperature of from -50°C to 15°C, preferably from -20°C to +12°C.

[0152] The ethylenically unsaturated monomers of the mixture (C) are preferably chosen such that the resulting polymer comprising seed, core and shell has an acid number of 10 to 25. Thus, mixture (C) preferably comprises at least one α,β-unsaturated carboxylic acid, especially (meth)acrylic acid.

[0153] The ethylenically unsaturated monomers of mixture (C) are further preferably selected such that the resulting polymer comprising seed, core and shell has an OH number of from 0 to 30, preferably from 10 to 25. All the above acid and OH values ​​are values ​​calculated based on the overall employed monomer mixture.

[0154] With particular preference, monomer mixture (C) comprises at least one α,β-unsaturated carboxylic acid, at least one monounsaturated ester of (meth)acrylic acid having an alkyl group substituted by a hydroxyl group and at least one monounsaturated ester of (meth)acrylic acid having an alkyl group.

[0155] Particularly preferably, neither monomer mixture (A) nor monomer mixture (B) or (C) comprises a polyurethane polymer having at least one polymerizable double bond.

[0156] After its preparation, the anionically stabilized polymer (asP) has an average particle size of 100 to 500 nm, preferably 125 to 400 nm, very preferably from 130 to 300 nm, and also has a glass transition temperature T of -20°C to -5°C. g .

[0157] The aqueous dispersion of the anionically stabilized polymer (asP) preferably has a pH of from 5.0 to 9.0, more preferably from 7.0 to 8.5, very preferably from 7.5 to 8.5.

[0158] The pH can be kept constant during the preparation, for example, by using a base as further confirmed below, or else can be deliberately set after the anionically stabilized polymer (asP) has been prepared. The described stages i. to iii. are preferably carried out without the addition of acids or bases known for setting the pH, and the pH is set only after the preparation of the polymer by adding organic nitrogen-containing bases, sodium bicarbonate, borates and also mixtures of the above substances.

[0159] The solids content of the aqueous dispersion of the anionically stabilized polymer (asP) is preferably from 15% to 40% and more preferably 20% to 30%.

[0160] Anionically stabilized polymers (asP) used in particular in the context of the present invention are preparable by reacting:

[0161] o a mixture (A) of 50 wt.-% to 85 wt.-% of a vinyl aromatic monomer and 15 wt.-% to 50 wt.-% of a monounsaturated ester of (meth)acrylic acid having an alkyl group,

[0162] o a mixture (B) of 1 to 4 wt.-% of a polyethylenically unsaturated monomer, 60 to 80 wt.-% of a monounsaturated ester of (meth)acrylic acid having an alkyl group and 16 to 39 wt.-% of a vinyl aromatic monomer, and

[0163] o a mixture (C) of 8 to 15 wt.-% of an α-β unsaturated carboxylic acid, 10 to 20 wt.-% of a monounsaturated ester of (meth)acrylic acid having an alkyl group substituted with a hydroxyl group, and 65 to 82 wt.-% of a monounsaturated ester of (meth)acrylic acid having an alkyl group,

[0164] in

[0165] i. firstly polymerizing the mixture (A),

[0166] ii. then polymerizing the mixture (B) in the presence of the polymer prepared according to i., and

[0167] iii. Thereafter the mixture (C) is polymerized in the presence of the polymer prepared according to ii.

[0168] The above figures (in wt.-%) are based in each case on the total weight of the mixture (A) or (B) or (C), respectively.

[0169] The anionically stabilized polymer (asP) dispersed in water, in other words the aqueous dispersion of the polymer (asP), advantageously has a defined electrophoretic mobility. Thus, it is preferred according to the invention that the anionically stabilized polymer (asP) dispersed in water has an electrophoretic mobility of -2.5 to -4 (μm / s) / (V / cm) at a pH of 8.0.

[0170] Furthermore, the coating composition may comprise anionically stabilized polymers (asP) in a total amount of 1 wt.-% to 30 wt.-%, preferably 5 wt.-% to 20 wt.-%, more particularly 5 wt.-% to 10 wt.-%, in each case based on the total solids content of the coating composition. The use of anionically stabilized polymers (asP) in the above-mentioned total amounts in combination with at least one non-polymeric polycarboxylic acid leads to a high flop index. Furthermore, the use of a binder leads to an effective fixation of the oriented effect particles EP during the flash evaporation of the coating composition of the invention, so that the high flop index is not adversely affected even when applying further layers of the coating composition.

[0171] As anionically stabilized polymer binder, the coating composition of the present invention may comprise at least one of the above-mentioned anionically stabilized polymers (asP) or the above-mentioned anionically stabilized polyurethane-polyurea particles (PPP). Preferably, the coating composition comprises at least one of the above-mentioned anionically stabilized polymers (asP) as anionically stabilized polymer binder and also the above-mentioned anionically stabilized polyurethane-polyurea particles (PPP). Particularly preferably, these polymers are present in the composition in a certain weight ratio. Therefore, according to the present invention, it is advantageous if the aqueous coating composition has a weight ratio of anionically stabilized polymers (asP) to anionically stabilized polyurethane-polyurea particles (PPP) of 1:10 to 1:1, more particularly 1:6 to 1:4.

[0172] Additional polymer binders

[0173] Besides at least one anionically stabilized polymer binder, the coating composition of the invention may comprise at least one further binder, more particularly at least one polymer selected from the group consisting of polyurethanes, polyesters, polyacrylates and / or copolymers of said polymers, more particularly polyesters and / or polyurethane polyacrylates.

[0174] The additional binder is different from the anionically stabilized polymer binder (PPP) and (asP). Preferred polyesters are described, for example, in DE 4009858 A1, column 6, line 53 to column 7, line 61 and column 10, line 24 to column 13, line 3, and in WO 2014 / 033135 A1, page 28, lines 13 to 33. The polymers described as binders are preferably hydroxy-functional and particularly preferably have an OH value in the range of from 20 to 200 mg KOH / g, more preferably from 50 to 150 mg KOH / g. More preferably, at least two mutually different hydroxy-functional polyesters are used as additional binders.

[0175] The total amount of all polymer binders is preferably from 9 to 60 wt.-%, more preferably from 20 to 50 wt.-% and most preferably from 30 to 45 wt.-%, based on the total weight of the aqueous coating material of the invention.

[0176] Cellulose nanofibers

[0177] In the literature, the term "cellulose nanofiber" may also be referred to as "cellulose nanofibrils", "fibrillated cellulose" or "nanocellulose crystals"; all of which are fiber-shaped. The term "cellulose nanofiber" is a general term that encompasses natural as well as functionalized cellulose nanofibers, such as carboxylated or sulphurized or otherwise modified and / or surface functionalized cellulose nanofibers. However, the backbone carrying such groups is always cellulose.

[0178] Of course, non-fibrous cellulose derivatives do not fall under the term "cellulose nanofibers". In particular, hydroxyalkylcelluloses such as those dissolved in aqueous media are not covered under the term "cellulose nanofibers" as used herein. Since these water-compatible cellulose types completely dissolve in water, they do exhibit different (molecular) sizes and therefore do show completely different rheological behaviors, suitable for wallpaper pastes, etc. (A. Goldschmidt, HJ Treitberger, BASF Handbook on Basics of Coatings Technology, 2003, Vincentz Network, pp. 47-49).

[0179] The cellulose nanofibers preferably have a number average fiber diameter in the range of preferably 2 to 800 nm, more preferably 2 to 500 nm, even more preferably 2 to 250 nm and most preferably 2 to 150 nm.

[0180] The cellulose nanofibers preferably have a number average fiber length in the range of preferably 0.04 to 20 μm, more preferably 0.04 to 15 μm, even more preferably 0.04 to 10 μm.

[0181] The aspect ratio determined by dividing the number average fiber length by the number average fiber diameter is preferably in the range of preferably 20 to 10,000, more preferably 20 to 5,000 and even more preferably 20 to 1,000.

[0182] The numerical averages of fiber length, diameter and aspect ratio of cellulose nanofibers were determined as specified in the experimental part of the present invention.

[0183] The cellulose nanofibers used can be those obtained by defiberizing a cellulose material and stabilizing it in water. Cellulose materials as used herein refer to cellulose primary materials in various forms. Specific examples include pulp (e.g., pulp derived from grass plants, such as wood pulp, jute, abaca and kenaf); natural cellulose, such as cellulose produced by microorganisms; regenerated cellulose obtained by dissolving cellulose in a copper ammonia solution, a solvent of a morpholine derivative, etc. and subjecting the dissolved cellulose to spinning; and fine cellulose obtained by subjecting a cellulose material to mechanical treatment (such as hydrolysis, alkaline hydrolysis, enzymatic decomposition, jet treatment, vibration ball milling, etc.) to depolymerize cellulose.

[0184] As long as the cellulosic material remains in a fibrous form, the method for defibration of the cellulosic material is not particularly limited. Examples of the method include mechanical defibration treatment using a homogenizer, a grinder, etc.; chemical treatment using an oxidation catalyst, etc.; and biological treatment using microorganisms, etc.

[0185] For cellulose nanofibers, anion-modified cellulose nanofibers can be used and preferably used. Examples of anion-modified cellulose nanofibers include carboxylated cellulose nanofibers, carboxymethylated cellulose nanofibers, sulfated cellulose nanofibers, and the like. Anion-modified cellulose nanofibers can be obtained, for example, by introducing functional groups such as carboxyl and carboxymethyl groups into a cellulose material by a known method, washing the obtained modified cellulose to prepare a dispersion of the modified cellulose, and defibring the dispersion. Carboxylated cellulose is also referred to as "oxidized cellulose".

[0186] For example, oxidized cellulose is obtained by oxidizing a cellulosic material in water using an oxidizing agent in the presence of a compound selected from the group consisting of N-oxyl compounds, bromides, iodides, and mixtures thereof.

[0187] The amount of the N-oxyl compound is not particularly limited as long as the amount is a catalytic amount that can disintegrate cellulose into nanofibers.

[0188] The amount of the bromide or iodide can be appropriately selected within the range in which the oxidation reaction is promoted.

[0189] As the oxidant, a known oxidant can be used. Examples include halogen, hypohalous acid, halogenous acid, perhalogen acid, salts thereof, halogen oxides, peroxides, and the like. It is preferred to set the conditions so that the amount of carboxyl groups in the oxidized cellulose is 0.2 mmol / g or more based on the solid content mass of the oxidized cellulose. For example, the amount of carboxyl groups can be adjusted by performing the following: adjusting the oxidation reaction time; adjusting the oxidation reaction temperature; adjusting the pH in the oxidation reaction; and adjusting the amount of N-oxyl compounds, bromides, iodides, oxidants, and the like.

[0190] Carboxymethylated cellulose can be obtained by mixing a cellulose material and a solvent, performing mercerization treatment using 0.5 to 20 times mole of an alkali metal hydroxide as a mercerizing agent per glucose residue of the cellulose material at a reaction temperature of 0°C to 70°C for a reaction time of about 15 minutes to 8 hours, and then adding 0.05 to 10.0 times mole of a carboxymethylating agent per glucose residue thereto, followed by reacting at a reaction temperature of 30°C to 90°C for a reaction time of about 30 minutes to 10 hours.

[0191] The degree of substitution of carboxymethyl groups per glucose unit in the modified cellulose obtained by introducing carboxymethyl groups into the cellulose material is preferably from 0.02 to 0.50.

[0192] The anion-modified cellulose thus obtained can be dispersed in an aqueous solvent to form a dispersion, and then defibrated with a pulverizer. The defibration method is not particularly limited. When carrying out mechanical defibration, the pulverizer used can be any of the following: a high-speed shearing pulverizer, a collision machine pulverizer, a bead mill pulverizer, a high-speed rotating pulverizer, a colloid mill pulverizer, a high-pressure pulverizer, a roller mill pulverizer, and an ultrasonic pulverizer. These pulverizers can be used in combination of two or more.

[0193] In addition, the cellulose obtained by neutralizing the above oxidized cellulose with an alkaline neutralizer can also be suitably used as a cellulose-based rheology control agent. This neutralizer is used to neutralize and improve the water-resistance of the rheology control agent (including cellulose nanofibers). The neutralizer used for oxidized cellulose in this specification is a neutralizer of an organic base larger than an inorganic metal salt group (such as sodium hydroxide). Preferred examples of neutralizers include organic bases, such as quaternary ammonium salts and amines (primary amines, secondary amines and tertiary amines). Preferred quaternary ammonium salts are quaternary ammonium alkalis. Examples of amines include alkylamines and alcoholamines. Examples of alkylamines include N-butylamine, N-octylamine, dibutylamine, triethylamine, etc. Examples of alcoholamines include N-butylethanolamine, N-methylethanolamine, 2-amino-2-methyl-1-propanol, dimethylethanolamine, dibutylethanolamine, methyldiethanolamine, etc.

[0194] The content of the neutralizing agent is not particularly limited as long as part or all of the oxidized cellulose can be neutralized. However, the content of the neutralizing agent is preferably 0.2 to 1.0 equivalent in terms of neutralization equivalent based on the contained acid groups.

[0195] The content of cellulose nanofibers is preferably in the range of 0.05 to 1.5 wt.-%, more preferably 0.06 to 1.0 wt.-% and most preferably 0.07 to 0.7 wt.-%, based on the total weight of the aqueous coating material of the present invention.

[0196] Examples of commercial products of cellulose nanofibers include Rheocrysta (registered trademark, produced by Dai-Ichi Kogyo Seiyaku Co., Ltd.); Cebina Fine (length 0.5 to 10 μm, diameter 15 to 100 nm), Celluforce NCV100 (length 44 to 108 nm, diameter 2.3 to 4.5 nm).

[0197] Non-polymeric polycarboxylic acid

[0198] The aqueous coating material of the present invention contains at least one non-polymeric polycarboxylic acid or a salt thereof, preferably at least one monomeric polycarboxylic acid or a salt thereof, even more preferably at least one monomeric dicarboxylic acid or a salt thereof.

[0199] According to the present invention, the term "polycarboxylic acid" refers to an aliphatic or aromatic carboxylic acid having at least two carboxylic acid groups per molecule, such as 2 to 4, more preferably 2 or 3 and most preferably 2 carboxylic acid groups. These carboxylic acid groups can be converted into anionic groups in whole or in part by a neutralizing agent.

[0200] The at least one non-polymeric polycarboxylic acid preferably has a melting point of 80 to 165°C, more preferably 85 to 150°C, preferably 90 to 140°C, more particularly 95 to 120°C.

[0201] The at least one non-polymeric polycarboxylic acid is most preferably a dicarboxylic acid.Dicarboxylic acids according to the invention are compounds having exactly two carboxylic acid groups per molecule.

[0202] In this context, particular preference is given to dicarboxylic acids having the general formula (I)

[0203] M +- OOC-R 1 -COO - M + (I)

[0204] in

[0205] Two M's + are independently monovalent cations, preferably selected from the group consisting of: H + , alkali metal cations (such as Na + , K + ), ammonium ion NH4 + Japanese formula N(R 2 )4 + The cation, where the residue R 2 are independently of one another H, an alkyl residue and a hydroxyalkyl residue, the alkyl residue preferably containing 1 to 6, more preferably 1 to 4, even more preferably 1 to 3 and most preferably 1 or 2, in particular 1, carbon atoms, and the hydroxyalkyl residue preferably containing 2 to 6, more preferably 2 to 4, even more preferably 2 to 3 and most preferably 2 carbon atoms; and

[0206] R 1 does not exist (i.e., M +- OOC-COO - M + ) or a divalent residue of a saturated or unsaturated, aliphatic or aromatic, linear, branched or cyclic hydrocarbon, the residue R 1 Preferably it comprises 1 to 72, preferably from 2 to 40, more preferably from 3 to 30, even more preferably from 3 to 18, more particularly 4 to 9, such as 4, 5, 6, 7 or 8 carbon atoms.

[0207] In R 1 In the case of residues containing more than 20, or even more than 30 carbon atoms, the residue R 1 Preferred are residues of dimer fatty acids, dimers and trimers being not considered as polymers herein.Such groups optionally and preferably contain one or more carbon-carbon double bonds and / or cyclic, in particular alicyclic hydrocarbon groups.

[0208] Preferred monovalent cations M + For example, the formula (CH3)2(alkyl-OH)NH + cations, such as protonated dimethylethanolamine.

[0209] The use of the abovementioned dicarboxylic acids, in particular azelaic acid, in combination with other mandatory ingredients and in the case of effect pigments contained in aqueous coating materials, is particularly advantageous for obtaining a high flop index without causing a reduction in the storage stability of the aqueous coating material part or adversely affecting the optical and color properties of the coatings produced from these compositions.

[0210] Polycarboxylic acids as used according to the invention are commercially available, for example from Merck.

[0211] At least one non-polymeric polycarboxylic acid is preferably used in a specific total amount. Therefore, it is particularly preferred according to the invention that the aqueous coating material comprises at least one non-polymeric polycarboxylic acid, more particularly a dicarboxylic acid of formula (I), in a total amount of 0.05 wt.-% to 5 wt.-%, preferably 0.10 wt.-% to 4 wt.-%, more preferably 0.20 wt.-% to 3 wt.-%, more particularly 0.25 wt.-% to 1 wt.-%, in each case based on the total weight of the coating material.

[0212] pigment

[0213] Preferably, the aqueous coating material of the present invention further comprises one or more pigments selected from the group consisting of color pigments and effect pigments.

[0214] Colored Pigments

[0215] Colored pigments are known to the person skilled in the art and are described, for example, in Rompp-Lexikon Lacke and Druckfarben, Georg Thieme Verlag, Stuttgart, New York, 1998, pages 176 and 451. The terms "coloring pigment" and "color pigment" are interchangeable.

[0216] Suitable colored pigments may be inorganic or organic pigments, and are preferably selected from the group consisting of: (i) white pigments such as titanium dioxide, zinc white, zinc sulfide or lithopone; (ii) black pigments such as carbon black, iron manganese black or spinel black; (iii) colored pigments such as ultramarine green, ultramarine blue, manganese blue, ultramarine violet, manganese violet, iron oxide red, molybdenum red, ultramarine red, iron oxide brown, mixed brown, spinel phase and corundum phase, iron oxide yellow, bismuth vanadate; (iv) organic pigments such as monoazo pigments, disazo pigments, anthraquinone pigments, benzimidazole pigments, quinacridone pigments, quinophthalone pigments, diketopyrrolopyrrole pigments, dioxazine pigments, indanthrone pigments, isoindoline pigments, isoindolinone pigments, azomethine pigments, thioindigo pigments, metal complex pigments, pyrenone pigments, perylene pigments, phthalocyanine pigments, aniline black; and (v) mixtures thereof.

[0217] One or more colored pigments are preferably used in a specific total amount. Therefore, in a preferred embodiment of the first subject of the present invention, the aqueous coating composition preferably comprises a total amount of colored pigments CP in an amount of 1 wt.% to 40 wt.%, preferably 2 wt.% to 35 wt.%, more preferably 5 wt.% to 30 wt.%, in each case based on the total weight of the coating composition.

[0218] Effect Pigments EP

[0219] The one or more effect pigments EP are preferably selected from the group consisting of lamellar aluminum pigments, aluminum pigments in the form of "corn flakes" and / or "silver dollars", aluminum pigments coated with organic pigments (e.g., aluminum pigments sold under the trade name "Friend ” is commercially available from Toyo Aluminum Co., Ltd. (Toyal), glass sheets (e.g., under the trade name “ )" are commercially available from Eckart), glass flakes coated with interference layers, gold bronze, oxidized bronze, iron oxide-aluminum pigments, pearlescent pigments, metal oxide-mica pigments, lamellar graphite, lamellar iron oxide, multilayer effect pigments consisting of PVD films and mixtures thereof, more particularly lamellar aluminum pigments.

[0220] In this context, if the layered aluminum pigment of passivation is used, it has been proved to be particularly advantageous. Therefore, it can be guaranteed that the water-based coating material of the present invention has high storage stability. Therefore, preferably, the layered aluminum pigment is processed with a passivating agent, and the passivating agent is selected from the group consisting of silane, organic polymer, chromium compound, phosphoric acid derivative, platinum derivative and mixture thereof, especially chromium compound. Derivative in this context is a compound wherein H atom or functional group has been replaced by another atom or another atomic group and / or wherein one or more atoms / atomic groups have been removed.

[0221] Furthermore, in this context, it has proven to be advantageous if the lamellar aluminum pigments have a defined flake thickness and an average particle size. The lamellar aluminum pigments preferably have a flake thickness of 200 to 500 nm and an average particle size D of 10 to 25 μm, more particularly 10 to 20 μm. 50 (For measurement methods, see the Examples section).

[0222] One or more effect pigments are preferably used in a specific total amount. Preferably, the aqueous coating material comprises at least one effect pigment EP, more particularly a lamellar aluminum pigment, in a total amount of 1 wt.-% to 20 wt.-%, preferably 2 wt.-% to 15 wt.-%, more preferably 2.5 wt.-% to 10 wt.-%, more particularly 3 wt.-% to 7 wt.-%, in each case based on the total weight of the coating material. The use of effect pigments, especially the above-mentioned lamellar aluminum pigments, in the stated total amounts, in combination with at least one polymer binder, preferably at least one anionically stabilized polymer binder and also at least one non-polymeric polycarboxylic acid and at least one cellulose nanofiber material, leads to particularly high flop indices, without, however, being detrimental to the other optical and coloristic properties of the coating.

[0223] filler

[0224] The waterborne coating material of the present invention preferably contains one or more fillers. The difference between filler and pigment is not important in the present invention. In order to distinguish the two, it is typically referred to the refractive index. If the refractive index is ≥1.7, the material is considered to be a pigment, and if the refractive index is <1.7, the material is considered to be a filler. The filler is preferably selected from the group consisting of carbonate, silicate such as talc, silicon dioxide such as precipitation or fumed silica and sulfate such as barium sulfate.

[0225] Additional components

[0226] In addition to the above-mentioned mandatory polymer binder PB, cellulose nanofibers CF and non-polymer polycarboxylic acid, the aqueous coating material of the present invention may also contain one or more additional components, such as a neutralizer, a thickener, a cross-linking agent and a solvent, and also other additives, such as a leveling agent, a dispersant, a wetting agent, a defoaming agent or a catalyst.

[0227] Neutralizer

[0228] The neutralizing agent is preferably selected from the group of inorganic bases, primary amines, secondary amines, tertiary amines and mixtures thereof, in particular dimethylethanolamine. Neutralizing agents, in particular dimethylethanolamine, are particularly preferably used to neutralize at least one non-polymeric polycarboxylic acid. In this way, the solubility of the non-polymeric polycarboxylic acid in the aqueous coating material can be increased.

[0229] In this context, it is preferred that at least one neutralizing agent, especially dimethylethanolamine, is present in a total amount of 0.25 wt.-% to 5 wt.-%, preferably 0.3 wt.-% to 4 wt.-%, more preferably 0.5 wt.-% to 3 wt.-%, more particularly 1 wt.-% to 3 wt.-%, in each case based on the total weight of the coating material. The use of a neutralizing agent, especially dimethylethanolamine, in the aforementioned amount range, in combination with at least one solvent L, ensures sufficient dissolution of the nonpolymeric polycarboxylic acid and thus ensures uniform incorporation of the coating material according to the invention and also high storage stability.

[0230] Thickener

[0231] The thickener is preferably selected from the group consisting of phyllosilicates, (meth)acrylic acid-(meth)acrylate copolymers, hydrophobically modified ethoxylated polyurethanes, hydrophobically modified polyethers, non-fibrous hydroxyalkylcelluloses, polyamides and mixtures thereof, in particular (meth)acrylic acid-(meth)acrylate copolymers and / or hydrophobically modified ethoxylated polyurethanes. (Meth)acrylic acid-(meth)acrylate copolymers are obtainable by reaction of (meth)acrylic acid with (meth)acrylate esters. Depending on the length of the carbon chain in the (meth)acrylate ester, these copolymers have an associative thickening effect (ASE or HASE thickeners). Copolymers containing only C1-C4 alkyl (meth)acrylates do not have an associative thickening effect (ASE thickeners). In contrast, copolymers containing (meth)acrylates with a chain length of more than four carbon atoms have an associative thickening effect (HASE thickeners). Hydrophobically modified ethoxylated polyurethanes are obtainable by reaction of diisocyanates with polyethers and subsequent reaction of the prepolymers with hydrophobic alcohols. Such polyurethanes are also referred to as HEUR thickeners. Particular preference is given to using a combination of non-associative thickening (meth)acrylic acid-(meth)acrylate copolymers and hydrophobically modified ethoxylated polyurethanes.

[0232] In this context, it is preferred that at least one thickener, more particularly a (meth)acrylic acid-(meth)acrylate copolymer and / or a hydrophobically modified ethoxylated polyurethane is present in a total amount of 0.015 wt.-% to 3 wt.-%, preferably 0.03 wt.-% to 2 wt.-%, more preferably 0.04 wt.-% to 1 wt.-%, more particularly 0.05 wt.-% to 0.7 wt.-%, in each case based on the total weight of the coating material.

[0233] According to a particularly preferred embodiment of the invention, the aqueous coating material does not contain phyllosilicates and / or polyamides, more particularly does not contain phyllosilicates and does not contain polyamides. This means that phyllosilicates and / or polyamides, more particularly phyllosilicates and polyamides are present in a total amount of 0 wt.-%, based on the total weight of the coating material. Surprisingly, the use of non-polymeric polycarboxylic acids without the additional use of polyamides and / or phyllosilicates results in a comparable flop index with the use of polyamides and / or phyllosilicates. However, when using at least one non-polymeric polycarboxylic acid, there is no undesirable separation phenomenon and no reduced shear stability.

[0234] Crosslinking agent

[0235] In case the mandatory polymer binder is a thermochemically curable binder, a crosslinking agent is typically present. The crosslinking agent is preferably selected from the group consisting of melamine-formaldehyde resins, polyisocyanates, blocked polyisocyanates, polycarbodiimides and mixtures thereof, especially melamine-formaldehyde resins.

[0236] In this context, it is preferred that the at least one crosslinking agent, in particular the melamine-formaldehyde resin, is present in a total amount of 1 wt.-% to 10 wt.-%, preferably 2 wt.-% to 6 wt.-%, more preferably 3 wt.-% to 5 wt.-%, more particularly 4 wt.-% to 6 wt.-%, in each case based on the total weight of the coating material. The above total amounts ensure sufficient crosslinking of the aqueous coating material.

[0237] Organic solvents

[0238] As a further component of the aqueous coating material of the invention, one or more organic solvents may be included in the coating material. Apart from the mandatory water, such solvents may be used in particular to dissolve the one or more non-polymeric polycarboxylic acids and thus allow a homogeneous incorporation of these.

[0239] The organic solvent is preferably selected from alkoxy-C2-C 10 Alcohols, ketones, esters, amides, methylals, butyrals, 1,3-dioxolane, glycerol formal and mixtures thereof, especially 1-methoxy-2-propanol.

[0240] The combined amount of water and one or more organic solvents is preferably in the range of 0.3 wt.-% to 30 wt.-%, preferably 1.5 wt.-% to 30 wt.-%, more preferably 3 wt.-% to 18 wt.-%, more particularly 6 wt.-% to 18 wt.-%, in each case based on the total weight of the coating material. The use of the above-mentioned amounts of at least one organic solvent and / or water can increase the solubility of the at least one non-polymeric polycarboxylic acid in the aqueous coating material.

[0241] Method for producing a multi-coat paint system

[0242] The present invention also provides a method for producing a multi-coat paint system on a substrate, the method comprising the following steps:

[0243] (1) optionally producing a cured first coating on a substrate by applying a coating material to the substrate and then curing the composition;

[0244] (2) producing one or more basecoats on the coating obtained in step (1) by applying one or more identical or different aqueous basecoat materials;

[0245] (3) producing one or more clear coat layers by applying a clear coat material over one or the topmost base coat layer; and

[0246] (4) co-curing the one or more basecoats and the one or more clearcoats;

[0247] in

[0248] At least one of the basecoat materials is a pigmented aqueous coating material according to the invention.

[0249] In the process of the invention, a multicoat paint system is built up on a substrate.

[0250] According to the present invention, preferably, the substrate is selected from metal substrates, plastics, glass and ceramics, more particularly from metal substrates.

[0251] The metal substrates contemplated include essentially substrates comprising or consisting of, for example, iron, aluminum, copper, zinc, magnesium and their alloys, and also steel in any very wide variety of forms and compositions. Preferred substrates are steel substrates, in particular typical steel substrates as used in the automotive industry sector. Prior to step (1) of the process of the invention, the metal substrate may be pretreated in a conventional manner - i.e., for example, cleaned and / or provided with a known conversion coating.

[0252] Suitable plastic substrates are in principle substrates which comprise or consist of (i) polar plastics such as polycarbonates, polyamides, polystyrenes, styrene copolymers, polyesters, polyphenylene oxides and blends of these plastics, (ii) reactive plastics such as PUR-RIM, SMC, BMC and also (iii) polyolefin substrates of the polyethylene and polypropylene type with a high rubber content, such as PP-EPDM and also surface-activated polyolefin substrates. The plastics may also be fiber-reinforced, more particularly with carbon fibers and / or metal fibers. Prior to step (1) of the method according to the invention, the plastic substrate may also be pretreated, more particularly by cleaning, in order to improve the adhesion of the first coating.

[0253] Furthermore, as substrates, those containing both metal and plastic parts can also be used. For example, a substrate of this kind is a car body containing plastic parts.

[0254] Step (1)

[0255] In step (1) of the process of the invention, a cured first coating can be produced on the substrate by applying the coating material to the substrate (S) and optionally subsequently curing it.

[0256] The coating material of step (1) can be an electrocoat coating material and can also be a primer coating material. However, the primer coating material according to the present invention is not the basecoat applied in step (2) of the method of the present invention.

[0257] The method of the present invention is preferably carried out with a metal substrate. Therefore, the first coating is preferably a cured electrocoat. Therefore, in a preferred embodiment of the method of the present invention, the coating material is an electrocoat coating material applied to the substrate by electrodeposition coating. For example, suitable electrocoat coating materials and also their curing are described in WO 2017 / 088988 A1.

[0258] Step (2)

[0259] In step (2) of the process according to the invention, one primer layer is produced (alternative 1) or two or more directly successive primer layers are produced (alternative 2).

[0260] These layers are produced by applying an aqueous basecoat material directly to the substrate (S) or directly to the cured coating obtained in step (1) or by applying two or more basecoat materials directly and successively to the substrate or to the cured coating obtained in step (1).

[0261] Thus, the basecoat according to alternative 1 of step (2) is arranged directly on the substrate or directly on the cured coating obtained in step (1), after it has been produced.

[0262] Applying two or more basecoat materials directly in succession to the cured coating obtained in step (1) (alternative 2) is understood as follows:

[0263] The application of the first basecoat material directly produces the first basecoat on the first coating of the solidification of step (1).Then directly produce the at least one other basecoat on the first basecoat.When producing two or more other basecoats, they are directly produced continuously.For example, an other basecoat can be produced just in time, in which case, in the multi-coat paint system finally produced, the basecoat is directly arranged below the first or unique clear coat.If two or more basecoats are applied, then it may be preferred that the first basecoat produced directly on substrate or directly on the first coating of solidification is based on color preparatory basecoat material.The second layer and the optional third layer are based on the same basecoat material for imparting color and / or imparting effect, or based on the first basecoat material for imparting color and / or imparting effect and based on different second basecoat materials for imparting color and / or imparting effect.

[0264] The basecoat material can be the same or different. It is also possible to produce two or more basecoats with the same basecoat material, and produce one or more other basecoats with one or more other basecoats. However, at least one of the employed water-based basecoat materials in step (2) comprises colored water-based coating material of the present invention.

[0265] According to alternative 1 of step (2) of the process according to the invention, a preferred embodiment in the context of the present invention encompasses the production of a basecoat layer.

[0266] The basecoat is not cured alone, but together with the clearcoat material. In particular, the coating material used in step (2) of the method of the invention is not cured alone like the coating material referred to as a surfacer in the context of the standard method. Therefore, in step (2), the basecoat is preferably not exposed to a temperature above 100° C. for a period of more than 1 minute, and particularly preferably not exposed to a temperature above 100° C. at all.

[0267] The basecoat material is applied so that after the curing in step (4), the basecoat and the separate basecoat each have a layer thickness of, for example, 5 to 50 microns, preferably 6 to 40 microns, and particularly preferably 7 to 35 microns. In the first alternative of step (2), it is preferred to produce a basecoat with a relatively high layer thickness of 15 to 50 microns, preferably 20 to 45 microns. In the second alternative of step (2), the separate basecoat tends to have a lower layer thickness by comparison, if only one basecoat is produced, the entire system still has a layer thickness within this order of magnitude. For example, in the case of two basecoats, the first basecoat preferably has a layer thickness of 5 to 35 microns, more particularly 10 to 30 microns, the second basecoat preferably has a layer thickness of 5 to 35 microns, more particularly 10 to 30 microns, and the overall layer thickness is preferably no more than 50 microns.

[0268] Step (3)

[0269] In step (3) of the method of the present invention, a clear coat is produced directly on a base coat or on the topmost base coat. This production is completed by applying a clear coat material accordingly. Suitable clear coat materials are described in, for example, WO 2006042585A1, WO 2009077182 A1 or in addition WO 2008074490 A1.

[0270] After application, the clearcoat material or the corresponding clearcoat is preferably flashed and / or intermediate dried at 15° C. to 35° C. for a period of 0.5 to 30 minutes.

[0271] The clearcoat material is applied in such a way that the layer thickness of the clearcoat after curing in step (4) is, for example, from 15 to 80 micrometers, preferably from 20 to 65 micrometers, particularly preferably from 25 to 60 micrometers.

[0272] Step (4)

[0273] In step (4) of the process of the invention, there is co-curing of the basecoat and the clearcoat or basecoats and clearcoats.

[0274] Co-curing is preferably carried out at a temperature of 100 to 250° C., preferably 100 to 180° C., for a duration of 5 to 60 minutes, preferably 10 to 45 minutes.

[0275] The process of the invention allows the production of multicoat paint systems on substrates without a separate curing step.

[0276] With regard to further preferred embodiments of the method according to the invention, in particular with regard to the basecoat materials used therein and the components of these basecoat materials, the statements made with regard to the coating materials according to the invention are valid mutatis mutandis.

[0277] Multi-coat paint systems

[0278] After completion of step (4) of the process according to the invention, the result is a multicoat paint system according to the invention.

[0279] Particularly preferably, the surface of the multicoat paint system has a flop index of 8 to 30, preferably 10 to 30, more particularly 12.5 to 30. This high flop index is achieved by using the pigmented aqueous coating material of the invention, despite the preferred absence of polyamide and / or phyllosilicate. In this context, the flop index achieved with the composition of the invention is comparable to the flop index of a composition that does contain polyamide and / or phyllosilicate.

[0280] With regard to further preferred embodiments of the multicoat paint system of the invention, the comments made with regard to the coating composition of the invention and also with regard to the method of the invention apply mutatis mutandis.

[0281] Uses of the present invention

[0282] A further subject matter of the present invention is the use of the unpigmented aqueous coating material according to the invention as a universal aqueous coating composition for producing the pigmented aqueous coating material according to the invention.

[0283] Yet another subject of the present invention is the use of at least one type of cellulose nanofibers as defined above together with one or more non-polymeric polycarboxylic acids and / or salts thereof as defined above in an aqueous coating material comprising one or more polymeric binders as defined above and one or more pigments as defined above for producing a multilayer coating system.

[0284] A further subject matter of the present invention is the use of the pigmented aqueous coating material of the invention as basecoat material.

[0285] The use mentioned above serves in particular to improve the flop index and the color matching compared to multicoat systems which comprise a pigmented aqueous basecoat which comprises no polyamide and / or layered metal silicate.

[0286] Subsequent color matching eliminates the need to dispose of aqueous coating compositions which are out of specification directly after production or due to storage and which therefore have to be disposed of. This leads to an improvement in the environmental balance and efficiency of basecoat production and also of the production of paint systems using these coating compositions.

[0287] With regard to further preferred embodiments of the use according to the invention, the comments made with regard to the coating material according to the invention, the method according to the invention and the multicoat paint system according to the invention are valid mutatis mutandis.

[0288] Experimental part / Example part

[0289] Method Description

[0290] Solids content (solids, non-volatile part)

[0291] The non-volatile fraction is determined according to DIN EN ISO 3251 (date: June 2008). This involves weighing 1 g of sample into an aluminum pan that has been previously dried, drying it in a drying cabinet at 125° C. for 60 minutes, allowing it to cool in a desiccator, and then reweighing. The residue corresponds to the non-volatile fraction relative to the total amount of sample used. If necessary, the volume of the non-volatile fraction can alternatively be determined according to DIN 53219 (date: August 2009).

[0292] Glass transition temperature T g

[0293] For the purposes of the present invention, the glass transition temperature T g Determined experimentally based on DIN 51005 "Thermal Analysis (TA)—Terms" and DIN 53765 "Thermal Analysis Dynamic Scanning Calorimetry (DSC)". This involves weighing 15 mg of sample into a sample boat and introducing it into the DSC instrument. After cooling to the starting temperature, the 1st and 2nd measurement runs are carried out with an inert gas purge (N2) of 50 ml / min at a heating rate of 10 K / min, wherein cooling to the starting temperature is performed again between the measurement runs. The measurement is generally carried out in a temperature range from about 50 ° C below the expected glass transition temperature to about 50 ° C above the glass transition temperature. For the purposes of the present invention, according to DIN 53765, Part 8.1, the glass transition temperature is the temperature at which half of the change in specific heat capacity (0.5Δc p ). This temperature is determined from the DSC graph (heat flow versus temperature graph). It is the temperature at the intersection of the midline between the extrapolated baselines and the measured curve before and after the glass transition.

[0294] granularity

[0295] According to DIN ISO 13321 (date: October 2004), the average particle size of spherical polymer particles is determined by dynamic light scattering (photon correlation spectroscopy (PCS)). Here, with respect to average particle size, it means the average particle diameter (Z-average value) measured. The measurement is carried out at 25°C ± 1°C using Malvern Nano S90 (from Malvern Instruments). The instrument covers a size range from 3 to 3000nm and is equipped with a 4mW He-Ne laser at 633nm. Each sample is diluted with particle-free deionized water as a dispersion medium, and then measured in a 1ml polystyrene cell with a suitable scattering intensity. With the help of Zetasizer analysis software version 7.11 (from Malvern Instruments), a digital correlator is used for evaluation. The measurement is carried out five times, and the measurement is repeated on a second freshly prepared sample. For aqueous dispersions of anionic stabilized polymers (asP), the average particle size refers to the arithmetic numerical mean of the average particle diameter (Z-average value; numerical mean) measured. For aqueous dispersions of anionically stabilized polyurethane-polyurea particles (PPP), the average particle size is the arithmetic mean of the average particle sizes (volume mean). The standard deviation of the five determinations here is ≤4%.

[0296] For cellulose nanofibers, the numerical average fiber diameter, length and thus calculated aspect ratio are obtained from atomic force microscopy (AFM) measurements. A representative sample of CNFs was imaged. In the resulting image, the diameter and fiber length of at least 100 fibers were determined. The aspect ratio is derived from the ratio of these values.

[0297] Determination of acid value

[0298] The acid number is determined using "Method A" according to DIN EN ISO 2114 (Date: June 2002). The acid number corresponds to the mass of potassium hydroxide in mg required to neutralize 1 g of sample under the conditions specified in DIN EN ISO 2114. The acid number reported here corresponds to the total acid number indicated in the DIN standard and is based on the solids content.

[0299] Determination of OH value

[0300] The OH value is determined according to DIN 53240-2 (date: November 2007). In this method, the OH groups are reacted by acetylation with excess acetic anhydride. The excess acetic anhydride is subsequently cleaved by adding water to form acetic acid, and all of the acetic acid is back-titrated with ethanolic KOH. The OH value indicates the amount of KOH (in mg) (based on solids) which is equal to the amount of acetic acid bound in the acetylation of 1 g of sample.

[0301] Determination of number average molecular weight and weight average molecular weight

[0302] The number average molecular weight (Ms) is determined by gel permeation chromatography (GPC) in accordance with DIN 55672-1 (date: August 2007). In addition to the number average molecular weight, this method can also be used to determine the weight average molecular weight (Mw) and also the polydispersity d (weight average molecular weight (Mw). w ) and number average molecular weight (M n ). Tetrahydrofuran was used as eluent. The determination was performed against polystyrene standards. The column material consisted of styrene-divinylbenzene copolymer.

[0303] Determination of Gel Fraction of Polyurethane-Polyurea Particles (PPP)

[0304] In the context of the present invention, the gel fraction of polyurethane-polyurea particles (PPP) is determined gravimetrically. Here, first, the polymer present is separated from a sample of an aqueous dispersion (initial mass 1.0 g) by freeze drying. After determining the curing temperature - above which the resistance of the sample does not show further changes when the temperature is further reduced - the completely frozen sample undergoes its main drying, typically in a drying vacuum pressure range between 5 mbar and 0.05 mbar, at a drying temperature 10°C lower than the curing temperature. Rapid freeze drying of the polymer is achieved by gradually increasing the temperature of the heated surface below the polymer to 25°C; after a typical drying time of 12 hours, the amount of separated polymer (solid fraction, determined via freeze drying) is constant and no longer undergoes any changes even during prolonged freeze drying. Subsequently drying at a temperature of 30°C of the surface below the polymer, the ambient pressure is reduced to the maximum extent (typically between 0.05 and 0.03 mbar), achieving optimal drying of the polymer.

[0305] The isolated polymer was subsequently sintered in a forced air oven at 130° C. for 1 minute and thereafter extracted in excess tetrahydrofuran at 25° C. for 24 hours (ratio of tetrahydrofuran to solid fraction=300:1). The insoluble fraction (gel fraction) of the isolated polymer was then separated off on a suitable glass frit, dried in a forced air oven at 50° C. for 4 hours, and then reweighed.

[0306] It was further determined that at a sintering temperature of 130°C, the gel fraction of the particles was found to be independent of the sintering time when the sintering time was varied between one minute and twenty minutes. Therefore, it can be ruled out that crosslinking reactions after the separation of the polymer solids further increase the gel fraction.

[0307] The gel fraction determined in this way according to the invention is also referred to as gel fraction (freeze drying).

[0308] In parallel, the gel fraction was determined gravimetrically by isolating a polymer sample from an aqueous dispersion (initial mass 1.0 g) at 130° C. for 60 minutes (solids content), also referred to below as gel fraction (130° C.). The mass of the polymer was determined, after which the polymer was extracted in an excess of tetrahydrofuran at 25° C. for 24 hours in a procedure similar to that described above, the insoluble portion (gel fraction) was separated off and dried and weighed.

[0309] Solubility in water

[0310] The solubility of an organic solvent in water at 20°C is determined as follows. The organic solvent in question and water are combined and mixed in a suitable glass container, and the mixture is then equilibrated. The amounts selected for water and solvent here are such that the equilibrium produces two phases separated from each other. After equilibration, a sample of the aqueous phase (i.e., the phase containing more water than the organic solvent) is collected using a syringe, and the sample is diluted with tetrahydrofuran at a ratio of 1 / 10 and subjected to gas chromatography to determine the fraction of the solvent (for conditions, see Section 8. Solvent content).

[0311] If two phases are not formed, the solvent is miscible with water in any weight ratio, regardless of the amounts of water and solvent. Thus, the infinitely water-soluble solvent (eg, acetone) is at least not a solvent (Z.2).

[0312] Determination of surface charge by electrophoresis

[0313] The surface charge was determined by measurement with a Zetasizer Nano from Malvern in the pH range of 3 to 10. The measurement was started at the pH of the sample after dilution. The pH was adjusted using HCl and / or NaOH. The samples were measured in 10 mmol / 1 KCl.

[0314] Isocyanate content

[0315] The isocyanate content, also referred to below as NCO content, is determined by adding an excess of a 2% N,N-dibutylamine solution in xylene to a homogeneous solution of the sample in acetone / N-ethylpyrrolidone (1:1 vol%) and potentiometric back titration of the excess amine with 0.1 N hydrochloric acid according to the method of DIN EN ISO 3251, DIN EN ISO 1 1909 and DIN EN ISO 14896. Via the fraction of polymer in solution (solids content), the NCO content of the polymer can be calculated back based on the solids content.

[0316] Neutralization

[0317] The degree of neutralization x of the component is calculated from the amount of substance of the carboxylic acid groups present in the component (determined via the acid number) and the amount of substance of the neutralizing agent used.

[0318] Amine equivalent mass

[0319] The amine equivalent mass (solution) is used to determine the amine content of a solution and is determined as follows. The sample under investigation is dissolved in glacial acetic acid at room temperature and titrated against 0.1 N perchloric acid in glacial acetic acid in the presence of crystal violet. From the initial mass of the sample and from the consumption of perchloric acid the amine equivalent mass (solution) is obtained: the mass of a solution of a basic amine required to neutralize one mole of perchloric acid.

[0320] The degree of blocking of primary amino groups

[0321] By means of IR spectroscopy, a Nexus FT-IR spectrometer (from Nicolet) was used with an IR cell (d=25 mm, KBr window) at 3310 cm -1 The absorption maximum at 1166 cm-1 at 25 °C is based on the concentration series of the amine used. -1 The degree of blocking of the primary amino groups was determined by standardizing to the absorbance maximum under the internal standard.

[0322] Determination of dry film thickness (dry layer thickness)

[0323] According to DIN EN ISO 2808 (date: May 2007) method 12A, using the 3100-4100 instruments determine film thickness.

[0324] Determination of the color flop index

[0325] To determine the brightness or the color flop index, a correspondingly coated substrate (such as the multi-coating system in Part 5 of the following working examples) is subjected to measurement using a spectrophotometer (e.g., an X-Rite MA60B+BA multi-angle spectrophotometer). The surface is irradiated with a light source. Spectral detection is performed in the visible light range at various angles. Taking into account the standardized spectral values ​​and also the reflection spectrum of the light source used, the spectral measurements obtained in this way can be used to calculate the color value in the CIEL*a*b* color space, where L* characterizes the brightness, a* characterizes the red-green value, and b* characterizes the yellow-blue value.

[0326] This method is described, for example, in ASTM E2194-12, in particular for coatings whose pigments comprise at least one effect pigment. A derived value, often used to quantify the so-called metallic effect, is the so-called flop index, which describes the relationship between brightness and viewing angle. From the brightness values ​​determined for viewing angles of 15°, 45° and 110°, the flop index (FI) can be calculated according to the formula xRite )

[0327]

[0328] Where L* represents the brightness value measured at the corresponding measurement angle (15°, 45° and 110°).

[0329] Storage stability measurement

[0330] To determine storage stability, the coating material was adjusted to a pH of 8.0 using deionized water and dimethylethanolamine and stored for 1000 s. -1 The coating material is adjusted to a spraying viscosity of 100±5 mPa*s under a shear load of 100° C., as measured at 23° C. using a rotational viscometer (Rheolab QC instrument with C-LTD80 / QC control system, from Anton Paar). Further measurements of the viscosity are carried out after storage for 4 weeks at 23° C. and after storage for 4 weeks at 40° C. If the change in viscosity after storage is small compared to the viscosity of the freshly prepared coating material, the coating material is considered to be storage-stable.

[0331] Working Example

[0332] The following examples of the present invention and comparative examples are used to illustrate the present invention but should not be construed as imposing any limitation.

[0333] With respect to the formulation components indicated and their amounts, the following factors should be considered: When reference is made to a commercial product or a preparation protocol described elsewhere, the reference (independent of the primary name chosen for the component in question) is to exactly that commercial product or exactly that product prepared using the protocol mentioned.

[0334] Thus, in case a formulation component has the main name "melamine-formaldehyde resin", and in case a commercial product is indicated for this component, the melamine-formaldehyde resin is used in the form of exactly this commercial product. Therefore, if a conclusion is to be drawn about the amount of active substance (melamine-formaldehyde resin), any additional components present in the commercial product, such as solvents, must be taken into account.

[0335] Thus, if a preparation recipe for a formulation component is mentioned, and if such preparation results in, for example, a polymer dispersion with a defined non-volatile fraction, then exactly this dispersion is used. The primary factor is not whether the main name that has been chosen is the term "polymer dispersion" or just the active substance, such as "polymer", "polyester", or "polyurethane-modified polyacrylate". This must be taken into account if conclusions are to be drawn about the amount of active substance (polymer).

[0336] 1. Production of polymer binder PM

[0337] 1.1 Anionically stabilized polymer dispersion D1

[0338] An anion-stabilized polymer (asP) dispersed in water was prepared according to the preparation example "BM2" on pages 63 to 66 of WO 2017 / 088988 A1. At a pH of 8, dispersion D1 had an electrophoretic mobility of -2.7 (μm / s) / (V / cm).

[0339] 1.2 Dispersion D2 of anionically stabilized polyurethane-polyurea particles (PPP)

[0340] Anion-stabilized polyurethane-polyurea particles (PPP) dispersed in water were prepared according to the preparation example "PD1" on pages 75 and 76 of WO 2018 / 011311 A1. At a pH of 8, dispersion D2 had an electrophoretic mobility of -6.7 (μm / s) / (V / cm).

[0341] 1.3 Dispersion D3 of anionically stabilized polyurethane particles

[0342] Anionically stabilized polyurethane particles dispersed in water were prepared according to Preparation Example H in DE 199 14 055 A1. At a pH of 8, dispersion D3 had an electrophoretic mobility of −3 (μm / s) / (V / cm).

[0343] 1.4 Dispersion D4

[0344] Anionically stabilized polyurethane-modified polyacrylates in water were prepared according to the preparation examples found in DE 4437535 A 1, page 7, line 55 to page 8, line 23.

[0345] At a pH of 8, dispersion D4 had an electrophoretic mobility of -4.2 (μm / s) / (V / cm).

[0346] 2. Preparation of CNF Solution

[0347] Cellulose nanofiber solution (CNF solution) was prepared from dry Celluforce NCV-100 by gradually adding solid CNF into deionized water while stirring vigorously. After reaching the desired amount of 3 wt.-% CNF in water, stirring was continued until a clear solution was formed.

[0348] 3. Preparation of filler paste and coloring paste

[0349] 3.1 Preparation of barium sulfate paste F1

[0350] Barium sulfate paste F1 was prepared from 54.00 parts by weight of barium sulfate (Blanc Fixe Micro, available from Sachtleben Chemie), 0.3 parts by weight of a defoamer (Agitan 282, available from Münzing Chemie), 4.6 parts by weight of 2-butoxyethanol, 5.7 parts by weight of deionized water, 3 parts by weight of a polyester (prepared according to Example D of DE A 4009858, column 16, lines 37-59) and 32.4 parts by weight of a polyurethane by professional grinding and subsequent homogenization.

[0351] 3.2 Preparation of talc paste F2

[0352] Talc paste F2 is composed of 28 parts by weight of talc (Micro Talc IT Extra, available from Mondo Minerals), 0.4 parts by weight of defoamer (Agitan 282, available from Mingling Chemical Company), 1.4 parts by weight of 184 (available from BYK Chemie, Wesel), 0.6 part by weight of acrylate thickener Rheovis AS130 (available from BASF SE), 1 part by weight of 2-butoxyethanol, 3 parts by weight of Pluriol P900 (available from BASF SE), 18.4 parts by weight of deionized water, 47 parts by weight of an acrylate polymer (binder dispersion A from application WO 91 / 15528 A1) and 0.2 part by weight of an aqueous dimethylethanolamine solution (10 wt.-% in water) are prepared by professional grinding and subsequent homogenization.

[0353] 3.3 Preparation of white paste coloring paste 1

[0354] A white paste is prepared from 50 parts by weight of Titan Rutil 2310 (from KRONOS WORLDWIDE, rutile type, produced using the chlorine process), 6 parts by weight of a polyester prepared in DE 40 09 858 A1 (Example D, column 16, lines 37-59), 24.7 parts by weight of a binder dispersion prepared in EP 022 8003 B2 (page 8, lines 6-18), 10.5 parts by weight of deionized water, 4 parts by weight of 2,4,7,9-tetramethyl-5-decynediol (52% in BG; from BASF), 4.1 parts by weight of butanediol, 0.4 parts by weight of 10% dimethylethanolamine in water and 0.3 parts by weight of Acrysol RM-8 (from The Dow Chemical Company) by a grinding process.

[0355] 3.4 Preparation of black paste coloring paste 2

[0356] The black paste was prepared from 57 parts by weight of a polyurethane dispersion prepared according to WO 92 / 15405, page 13, line 13 to page 15, line 13, 10 parts by weight of carbon black (from Cabot Corporation) 1400 carbon black), 5 parts by weight of a polyester prepared according to Example D of DE 40 09 858 A1, column 16, lines 37-59, 6.5 parts by weight of a 10% strength aqueous solution of dimethylethanolamine, 3 parts by weight of a commercial polyether ( P900, available from BASF), 7 parts by weight of butyl diglycol and 11 parts by weight of deionized water.

[0357] 3.5 Preparation of light yellow paste coloring paste 3

[0358] A pale yellow paste was prepared with 49 parts by weight of a polyurethane dispersion prepared according to Binder Dispersion A of WO 92 / 15405, 8.0 parts by weight of Disperbyk 184 commercially available from BYK, 37 parts by weight of Bayferrox 3910 commercially available from Lanxess and 6 parts by weight of completely desalinated water.

[0359] 3.6 Preparation of blue paste coloring paste 4

[0360] The red paste was prepared with 52.04 parts by weight of a polyurethane dispersion prepared according to the binder dispersion A of WO 92 / 15405, 4.0 parts by weight of Disperbyk 184 commercially available from BYK Chemicals, 0.3 parts by weight of a defoamer Agitan 282 commercially available from Mingling Chemicals, 33.03 parts by weight of Heucodur Blue 550 commercially available from Heubach GmbH, 5.6 parts by weight of completely desalinated water, 3 parts by weight of propylene glycol ether and 3 parts by weight of a polyether commercially available from BASF. P900 was prepared together with 2 parts by weight of a 10 wt. % acrylic acid-based thickener Rheovis AS130 (BASF) in demineralized water.

[0361] 4. Production of water-based coating materials

[0362] Unless stated otherwise, amounts in parts by weight and amounts in percentages are in each case percentages by weight.

[0363] 4.1 Production of water-based base coating materials BL1* to BL4

[0364] To produce the mixed varnish ML, melamine slurry and aluminum pigment slurry, the corresponding components in the following table were homogenized at room temperature. The polycarboxylic acid preparation was produced by homogenizing the non-polymeric polycarboxylic acid in solvent L and adding the neutralizer at room temperature. The polyamide wax dispersion was produced by homogenizing the polyamide in the corresponding amount of deionized water at room temperature under stirring.

[0365] The water-based basecoat material is produced as follows:

[0366] (a) homogenizing the mixed varnish ML and melamine slurry at room temperature,

[0367] (b) homogenizing successively the ingredients listed in the table under the entry "Basecoat components" in the order stated therein with the mixture obtained according to (a),

[0368] (c) homogeneously mixing the aluminum pigment slurry into the mixture obtained according to (b) under stirring at room temperature,

[0369] (d) successively and homogeneously incorporating into the mixture obtained according to (c) the ingredients listed in the table under the entry "Additive components" in the order stated therein, and

[0370] (e) homogeneously incorporating the polycarboxylic acid preparation (if any) into the mixture obtained according to (d).

[0371] The composition was then adjusted to a pH of 7.8 to 8.2 using deionized water and dimethylethanolamine and heated for 1000 s. -1 The spraying viscosity is adjusted to 100±5 mPa*s under a shear load of 100° C., as measured at 23° C. using a rotational viscometer (Rheolab QC instrument with C-LTD80 / QC control system, from Anton Paar), without the viscosity falling below the above value.

[0372] Table 1

[0373]

[0374] *Comparative Examples 1 52 wt.-% in butanediol (BASF)

[0375] 2 Anionically stabilized polymer binder (aqueous dispersion of anionically stabilized polymer asP)

[0376] 3 Melamine-formaldehyde resin

[0377] 4 Prepared according to WO2014 / 033135, page 28, 11.13-33, Example BE1

[0378] 5 Anionically stabilized polymer binder (aqueous dispersion of anionically stabilized polyurethane-polyurea particles PPP)

[0379] 6 BASF

[0380] 7 BASF

[0381] 8 Alu-Stapa Hydromic 2156 (65 wt.-% pigment, commercially available from Altana-Eckart)

[0382] 9 Alu-Stapa Hydromic 2192 (65 wt.-% pigment, commercially available from Altana-Eckart)

[0383] 10 Prepared according to DE-A-4009858, col. 16, ll.37-59, Example D

[0384] 11 Commercially available from King Industries

[0385] 12 Commercially available from Evonik

[0386] 13 Commercially available from BYK Chemical GmbH

[0387] 14 A dicarboxylic acid of formula (I) wherein R 1 =(CH2)4

[0388] 15 Diethanolamine

[0389] 16 Cellulose nanofiber (CNF) - solution (3% in water) (commercial name of the fiber: Celluforce NCV-100)

[0390] 4.2 Production of water-based base coating materials BL5* to BL10

[0391] Aqueous basecoat materials BL5* to BL1 = produced as described in section 4.1. However, the components used were those from the following table (superscript numbers have the same definition as in the table in section 4.1).

[0392] Table 2

[0393]

[0394]

[0395] 5. Production of multi-coat paint systems

[0396] 5.1 Multi-coat paint systems using BL1*, BL2, BL3 and BL4

[0397] Standard cathodic electrocoating materials (from BASF Coatings) 500 gray), the steel panels were coated with a standard commercial surface coating agent (UniBlock FC737555, available from BASF Coatings GmbH) in two spray passes using ESTA bell (ECO Bell 1 from ABB), and after a flash-off time of 10 minutes at 23° C., the panels thus coated were subsequently cured at 150° C. for 20 minutes; the resulting dry layer thickness was about 35 μm.

[0398] Subsequently, the corresponding waterborne basecoat material was applied in two spray passes using an ESTA bell (ECO Bell 6-F), with a flash of 45 seconds between each spray pass. The panels were then flashed at 23° C. for 10 minutes and subsequently dried at 80° C. for 10 minutes. The resulting total dry layer thickness of the corresponding coating material was about 14 μm.

[0399] After the basecoat material had dried, a commercial clearcoat material (DuraGloss FF700025, available from BASF Coatings) was applied using a bell (Eco Bell 1) and, after a flash-off time of 10 minutes at 23° C., subsequently cured at 150° C. for 20 minutes; the resulting dry layer thickness was about 40 μm. The clearcoat material was applied according to DIN EN ISO 2808 (date: May 2007), method 12A, using the clearcoat from ElektroPhysik GmbH. 3100-4100 instruments determine layer thickness.

[0400] 5.2 Multi-coat paint system using BL5* or BL6 as the first basecoat material and BL7*, BL9* and BL10 as the second basecoat material

[0401] The standard cathode electrocoating material (from BASF Coatings) was used. 800gray) steel plate.

[0402] The first basecoat material was applied using an ESTA bell (EcoBell 3). The panel was then flashed at 23° C. for 4 minutes. The resulting total layer thickness of the corresponding coating material was about 12 μm.

[0403] Thereafter, the second primer layer was first applied using the same ESTA bell type (EcoBell 3) to give a layer thickness of about 10 μm. Subsequently, a layer of about 4 μm of the second primer layer was applied using pneumatic application using an AGMD Devilbiss bell. After flashing at 23° C. for 4 min, the film was dried at 80° C. for 10 min.

[0404] After the basecoat material had dried, a commercial clearcoat material (ProGloss FF990365, available from BASF Coatings) was applied using a bell (Eco Bell 2) and, after a flash time of 5 minutes at 23° C., subsequently cured at 140° C. for 20 minutes; the resulting dry layer thickness was about 42 μm.

[0405] 6. Results

[0406] 6.1 Storage stability

[0407] The base coating materials BL2 (pH: 8; total solids: 30 wt.-%; CNF solids: 0.5 wt.-%), BL3 (pH: 8; total solids: 31 wt.-%; CNF solids: 0.3 wt.-%) and BL4 (pH: 8; total solids 30 wt.-%; CNF solids: 0.16 wt.-%) of the present invention were subjected to the above-mentioned storage stability test, and the results are shown in Table 3 below.

[0408] Table 3

[0409]

[0410] On the one hand, the viscosity stability is much higher by using CNFs compared to lower CNF solids concentrations (compare BL4 vs. BL3 vs. BL2), and on the other hand, especially compared to comparative example BL 1. Whereas comparative BL1 shows a viscosity increase of 239% after 4 weeks storage at 40°C, BL2 shows only a slight change of 16%, wherein a measurement error of 10% must be taken into account.

[0411] Comparative effect pigments containing base coating material BL7* (pH: 8; total solids: 21.2 wt.-%; CNF solids: 0.0 wt.-%; polycarboxylic acid solids: 0.0 wt.-%), comparative effect pigments containing base coating material BL8* (pH: 7.9; total solids: 20.9 wt.-%; CNF solids: 0.5 wt.-%; polycarboxylic acid solids: 0.0 wt.-%), comparative effect pigments containing base coating material BL9* (pH: 7.8; total solids: 19.8 wt.-%; CNF solids: 0.0 wt.-%; polycarboxylic acid solids: 0.1 wt.-%) and effect pigments according to the invention containing base coating material BL10 (pH: 8; total solids: 19.4 wt.-%; CNF solids: 0.5 wt.-%; polycarboxylic acid solids: 0.1 wt.-%) were subjected to the above-described storage stability test, the results of which are shown in Table 4 below.

[0412] Table 4

[0413]

[0414] The CNF based basecoat showed a lower viscosity drop after 4 weeks at 40°C compared to BL9 and BL10. The viscosity drop was 22% while the viscosity drop of the comparable LRD based CNF free system was 39%. This means that the stored product has a better stability against sagging.

[0415] 6.2 Angle-of-view color index

[0416] Comparative basecoat BL1* (pH: 8; total solids: 30 wt.-%; CNF solids: 0.0 wt.-%; polycarboxylic acid solids: 0.3 wt.-%) and basecoat materials of the invention BL2 (pH: 8; total solids: 30 wt.-%; CNF solids: 0.5 wt.-%; polycarboxylic acid solids: 0.3 wt.-%), BL3 (pH: 8; total solids: 31 wt.-%; CNF solids: 0.3 wt.-%; polycarboxylic acid solids: 0.3 wt.-%) and BL4 (pH: 8; total solids 30 wt.-%; CNF solids: 0.16 wt.-%; polycarboxylic acid solids: 0.3 wt.-%) were used in the production of the multi-coat system as described in Section 5 above. The results are shown in Table 5 below.

[0417] Table 5

[0418]

[0419] The above basecoat materials BL2, BL3 and BL4 were used in the same multilayer coating system and differed in that they contained different amounts of cellulose nanofiber solids, namely 0.5 wt.-%, 0.3 wt.-% and 0.16 wt.-%, all based on the total weight of the respective basecoat materials. Table 5 clearly shows that the amount of solids of cellulose nanofibers has only a small effect on the flop index. If anything, even the use of a higher amount in BL2 does not have a negative impact on the flop index, on the contrary, the flop index is even a little higher compared to BL3 and BL4. Moreover, in all three inventive examples, the flop index is increased compared to the comparative example BL1* using layered metal silicate.

[0420] The multi-coat systems as shown in Table 6 below comprised two basecoats and were prepared as detailed in Section 5.2 above. The first basecoat material was either comparative basecoat material BL5* (pH: 8.6; total solids: 34 wt.-%; CNF solids: 0.0 wt.-%; polycarboxylic acid solids: 0.0 wt.-%) - for Examples C1 and C2 - or inventive basecoat material BL6 (pH: 8.4; total solids: 34 wt.-%; CNF solids: 0.3 wt.-%; polycarboxylic acid solids: 0.1 wt.-%) - for Examples I1 and I2.

[0421] A second primer layer is applied wet on wet over the top or first primer layer.

[0422] The second basecoat was prepared from a comparative effect pigment containing basecoat material BL7* (pH: 8.0; total solids: 21.2 wt.-%; CNF solids: 0.0 wt.-%; polycarboxylic acid solids: 0.0 wt.-%) - for example C1 -, a comparative effect pigment containing basecoat material BL8* (pH: 7.9; total solids: 20.9 wt.-%; CNF solids: 0.5 wt.-%; polycarboxylic acid solids: 0.0 wt.-%) - for examples C2 and I1 -, or an effect pigment according to the invention containing basecoat material BL10 (pH: 8.0; total solids: 19.4 wt.-%; CNF solids: 0.5 wt.-%; polycarboxylic acid solids: 0.1 wt.-%) - for example I2. The results are shown in Table 6 below.

[0423] Table 6

[0424]

[0425] *Coating not according to the invention

[0426] a Layered metal silicates

[0427] b Cellulose nanofibers

[0428] In all of the above Examples C1, C2, I1 and I2, only the second basecoat layer contains metallic effect pigments, whereas the first basecoat layer contains only colour pigments but no metallic effect pigments (see Table 2).

[0429] In Comparative Example C1, both layers use layered metal silicate (LMS) as rheology control agent, and no non-polymeric polycarboxylic acid is contained in either layer of the two primers. The flop index is the lowest flop index (14.0) compared to the other examples. In Comparative Example C2, the same first primer as Comparative Example C1 is used, followed by a second primer containing cellulose nanofibers instead of layered metal silicate but without non-polymeric polycarboxylic acid. The flop index is slightly improved (14.6).

[0430] Inventive Example I1 shows that the use of the inventive basecoat formed from basecoat material BL6 already and surprisingly easily increases the flop of the combined double basecoat structure, and the layer containing the metal effect pigment does not contain a non-polymeric polycarboxylic acid. The flop index is 15.5. The best results are provided in Inventive Example I2, i.e., both basecoats (colored layer and metallic effect colored layer) contain cellulose nanofibers and a non-polymeric polycarboxylic acid, thus providing a flop index of 16.7.

Claims

1. A water-based coating material comprising a) one or more polymer binders; b) one or more types of cellulose nanofibers; and c) one or more non-polymeric polycarboxylic acids and / or salts thereof.

2. The water-based coating material according to claim 1, further comprising d) one or more pigments selected from the group consisting of color pigments and effect pigments.

3. The water-based coating material according to claim 1 or 2, characterized in that: One of the one or more polymeric binders includes one or more anionically stabilized polymeric binders.

4. The aqueous coating material according to any one or more of claims 1 to 3, wherein The one or more types of cellulose nanofibers are selected from the group consisting of anionically modified cellulose nanofibers.

5. The aqueous coating material according to any one or more of claims 1 to 3, wherein The anionically modified cellulose nanofibers contain sulfate groups.

6. The water-based coating material according to any one of claims 1 to 5, wherein The one or more types of cellulose nanofibers have a diameter ranging from 2 to 500 nm and a length ranging from 0.04 to 20 μm.

7. According to any one or more of the aqueous coating materials in claims 1 to 6, the one or more non-polymeric polycarboxylic acids and / or their salts have the following general formula (I): M +- OOC-R 1 -COO - M + (I) in Two M's + are independently monovalent cations, and R 1 There are no divalent residues that are either saturated or unsaturated, aliphatic or aromatic, straight chain, branched or cyclic hydrocarbons.

8. The water-based coating material according to claim 7, wherein: The monovalent cation is selected from H + , alkali metal cations, NH4 + Japanese formula N(R 2 )4 + The group of cations, where the residue R 2 are independently H, an alkyl residue and a hydroxyalkyl residue; and R 1 Absent or containing 1 to 72 carbon atoms.

9. The aqueous coating material according to any one or more of claims 2 to 8, wherein: The one or more colored pigments are selected from the group consisting of: (i) white pigments, such as titanium dioxide, zinc white, zinc sulfide or lithopone; (ii) black pigments such as carbon black, iron manganese black or spinel black; (iii) colour pigments such as ultramarine green, ultramarine blue, manganese blue, ultramarine violet, manganese violet, iron oxide red, molybdenum red, ultramarine red, iron oxide brown, mixed brown, spinel and corundum phases, iron oxide yellow, bismuth vanadate; (iv) organic pigments such as monoazo pigments, disazo pigments, anthraquinone pigments, benzimidazole pigments, quinacridone pigments, quinophthalone pigments, diketopyrrolopyrrole pigments, dioxazine pigments, indanthrone pigments, isoindoline pigments, isoindolinone pigments, azomethine pigments, thioindigo pigments, metal complex pigments, pyrene pigments, perylene pigments, phthalocyanine pigments, and aniline black; and (v) mixtures thereof, and / or The one or more effect pigments are selected from the group consisting of: (vi) lamellar aluminum pigments, aluminum pigments in the form of "corn flakes" and / or "silver dollars", aluminum pigments coated with organic pigments (vii) glass flakes, glass flakes coated with an interference layer, (viii) Gold bronze, oxidized bronze, (ix) Iron oxide-aluminum pigments, pearlescent pigments, metal oxide-mica pigments, lamellar graphite, flake iron oxide, multilayer effect pigments consisting of PVD films, and mixtures thereof.

10. according to any one or more of the aqueous coating materials in claims 1 to 9, it comprises the gross weight based on the aqueous coating material, 9 wt.-% to 60 wt.-% of the one or more polymeric binders; 0.05 wt.-% to 1.5 wt.-% of the one or more types of cellulose nanofibers; and 0.05 wt.-% to 5 wt.-% of the one or more non-polymeric polycarboxylic acids and / or their salts.

11. The aqueous coating material according to claim 910, further comprising from 1 wt.-% to 40 wt.-% of the one or more colored pigments, based on the gross weight of the aqueous coating material; and / or 1 wt.-% to 20 wt.-% of the one or more effect pigments.

12. Aqueous coating composition according to any one or more of claims 1 to 11, having a solids content in the range from 10 wt.-% to 65 wt.-%.

13. A method for producing a multi-coat paint system on a substrate, the method comprising the steps of: (1) optionally producing a cured first coating on the substrate by applying a coating material to the substrate and subsequently curing the composition; (2) producing one or more basecoats on the coating obtained in step (1) by applying one or more identical or different aqueous basecoat materials; (3) producing one or more clear coat layers by applying a clear coat material over one or the topmost base coat layer; as well as (4) curing the one or more basecoats and the one or more clearcoats together; in At least one of the basecoat materials is an aqueous coating material according to any one or more of claims 2 to 12 .

14. A multi-layer coating system obtainable by the method according to claim 13.

15. Use of the aqueous coating material according to claim 1 as a universal aqueous coating composition for producing the colored aqueous coating material according to claims 2 to 12.

16. Use of at least one type of cellulose nanofibers as defined in claims 1 to 12 together with one or more non-polymeric polycarboxylic acids and / or their salts as defined in claims 1 to 12 in an aqueous coating material comprising one or more polymeric binders as defined in claims 1 to 12 and one or more pigments as defined in claims 2 to 12 for producing a multilayer coating system.

17. Use of a pigmented aqueous coating material according to any one or more of claims 2 to 12 as basecoat material.

Citation Information

Patent Citations

  • water-dilutable coating agent

    DE19914055A1

  • basecoat and its use for producing color and / or effect basecoats and multicoat paint systems

    DE19930665A1

  • Aqueous pigmented base lacquer containing a water-dilutable polyacrylate resin as a binder and use of such a base lacquer

    DE4009858A1

  • polyurethane modified polyacrylate

    DE4437535A1

  • Preparation of a multilayer coating

    EP0228003B2